Method for manufacturing substrate with silicon through electrode, substrate with silicon through electrode, and copper paste for forming silicon through electrode
Patent Information
- Application Number
- CN201980095649.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-04-24
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2039-04-24
AI Technical Summary
[0047] According to one aspect of the present invention, a method for manufacturing a substrate having a silicon through-electrode with high productivity, having sufficient conductivity and excellent connection reliability, a substrate having a silicon through-electrode with sufficient conductivity and excellent connection reliability, and a copper paste for forming the silicon through-electrode are provided.
Smart Images

Figure CN113711337B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a substrate having a silicon through-electrode, a substrate having a silicon through-electrode, and a copper paste for forming the silicon through-electrode. Background Technology
[0002] In recent years, in order to achieve miniaturization, high functionality and integration of electronic devices or components, three-dimensional mounting technology, which connects silicon substrates arranged on top and bottom via electrodes called through-silicon electrodes (TSVs) and stacks semiconductor chips in a high density in the vertical (height direction), has attracted much attention.
[0003] As a method for forming silicon through-hole electrodes, for example, Patent Document 1 discloses a method for manufacturing a semiconductor device having silicon through-hole electrodes, which includes a step of plating copper on a non-through-hole formed on a silicon substrate by electroplating with a specific copper plating solution.
[0004] Previous technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-16712 Summary of the Invention
[0007] The technical problem to be solved by the invention
[0008] However, the method described in Patent Document 1 requires suppressing the deposition rate of the copper coating during the plating process, which increases the processing time and causes problems in terms of productivity.
[0009] On the other hand, substrates with silicon through electrodes are required to not only have sufficient conductivity, but also excellent connection reliability in which the resistance value does not easily increase under temperature changes.
[0010] Therefore, one aspect of the object of the present invention is to provide a method for manufacturing a substrate having a silicon through electrode with high productivity, having sufficient conductivity and excellent connection reliability, a substrate having a silicon through electrode with sufficient conductivity and excellent connection reliability, and a copper paste for forming the silicon through electrode.
[0011] means for solving technical problems
[0012] To achieve the aforementioned objective, the inventors conducted repeated and in-depth research, and discovered that after forming a copper sintered body with a porous structure within the through-hole of a substrate having a silicon through-hole electrode, a curable resin composition was impregnated within the copper sintered body, and then cured to form a conductor comprising a copper sintered body with the resin curing material filling the pores, and a silicon through-hole electrode comprising a conductor filled into the through-hole was provided. Furthermore, the inventors discovered that a substrate with a silicon through-hole electrode through which the through-hole is filled with this conductor exhibits a sufficiently low initial resistance value, and the resistance value does not easily increase even during temperature cycling connection reliability tests, thus completing the present invention.
[0013] That is, one aspect of the present invention provides the following invention.
[0014] [1] A method for manufacturing a substrate having a silicon through-electrode, comprising:
[0015] Preparation process: Prepare a silicon substrate, which includes a silicon wafer with through holes, the through holes being formed on two main surfaces.
[0016] The copper sintered body forming process forms a copper sintered body with a porous structure by at least filling the aforementioned through holes;
[0017] The resin impregnation process involves impregnating the above-mentioned copper sintered body with a curable resin composition;
[0018] In the resin curing process, the curable resin composition impregnated in the copper sintered body is cured to form a conductor comprising the copper sintered body with pores filled with the cured resin, and a silicon through-hole electrode is provided in the through-hole.
[0019] [2] A method for manufacturing a substrate having a silicon through-electrode, comprising:
[0020] Preparation process: Prepare a silicon substrate, which includes a silicon wafer having non-through holes, with the non-through holes opening on a main surface.
[0021] The copper sintered body forming process forms a copper sintered body with a porous structure by at least filling the aforementioned non-penetrating holes.
[0022] The resin impregnation process involves impregnating the above-mentioned copper sintered body with a curable resin composition;
[0023] The resin curing process involves curing the curable resin composition impregnated in the copper sintered body to form a conductive body comprising the copper sintered body with porous structures filled with cured resin; and
[0024] In the grinding process, a silicon through electrode is provided by grinding the side of the silicon substrate on which the above-mentioned conductive material is formed, opposite to the side with the above-mentioned non-through hole.
[0025] [3] According to the method of [1] or [2], wherein the filling rate of the resin cured material in the conductor is 80% or more by volume, based on the volume of the internal space of the porous structure.
[0026] [4] The method according to any one of [1] to [3], wherein the porosity of the copper sintered body is 1 to 15% by volume, based on the volume of the copper sintered body.
[0027] [5] The method according to any one of [1] to [4], wherein, in the copper sintered body forming process, the copper sintered body is formed in such a way that it covers at least a portion of the main surface of the silicon substrate.
[0028] [6] The method according to [5] further comprises a conductor removal step, which removes at least a portion of the conductor formed on the main surface of the silicon substrate.
[0029] [7] According to the method described in [6], the removal method in the above-mentioned conductor removal process is selected from one or more of the group consisting of etching, mechanical polishing and chemical mechanical polishing.
[0030] [8] The method according to any one of [1] to [7], wherein the silicon substrate has at least a metal coating disposed on the wall surface of the through hole.
[0031] [9] The method according to any one of [1] to [8], wherein the ratio of the length L of the silicon through electrode to the aperture D, L / D, is 10 or more.
[0032]
[10] The method according to any one of [1] to [9], wherein the copper sintered body forming step comprises:
[0033] The copper paste filling process involves filling the aforementioned through-holes in the silicon substrate with copper paste containing copper particles; and
[0034] The copper paste firing process involves firing the aforementioned copper paste to form the aforementioned sintered copper body.
[0035]
[11] According to the method of
[10] , wherein the copper paste comprises a first copper particle with a particle size of 0.8 μm or more and a second copper particle with a particle size of 0.5 μm or less as the copper particles.
[0036]
[12] According to the method described in
[11] , the first copper particle is flat.
[0037]
[13] The method according to any one of
[10] to
[12] , wherein the copper paste is fired under a pressure of 0.1 MPa or higher.
[0038]
[14] The method according to any one of
[10] to
[13] , wherein the copper paste is fired in an environment containing nitrogen or hydrogen.
[0039]
[15] A substrate having a silicon through-hole electrode comprises: a silicon substrate including a silicon wafer having a through-hole, the through-hole being formed through two main surfaces; and a silicon through-hole electrode including a conductor filling the through-hole, the conductor including a copper sintered body having a porous structure and a resin cured material filling the pores of the copper sintered body.
[0040]
[16] The substrate having a silicon through electrode according to
[15] , wherein, based on the volume of the porous internal space, the filling rate of the resin cured material in the conductor is 80% by volume or more.
[0041]
[17] The substrate having a silicon through-hole electrode according to
[15] or
[16] , wherein the silicon substrate has a metal coating at least disposed on the wall surface of the through-hole.
[0042]
[18] A substrate having a silicon through-hole electrode according to any one of
[15] to
[17] , wherein the ratio of the length L of the silicon through-hole electrode to the aperture D, L / D, is 10 or more.
[0043]
[19] A substrate having a silicon through electrode according to any one of
[15] to
[18] , wherein the conductor covers at least a portion of the main surface of the silicon substrate.
[0044]
[20] A copper paste for forming a silicon through electrode, which is a copper paste for forming a silicon through electrode, the copper paste for forming a silicon through electrode includes a first copper particle with a particle size of 0.8 μm or more and a second copper particle with a particle size of 0.5 μm or less.
[0045]
[21] According to the copper paste described in
[20] , wherein the first copper particle is flat.
[0046] Invention Effects
[0047] According to one aspect of the present invention, a method for manufacturing a substrate having a silicon through-electrode with high productivity, having sufficient conductivity and excellent connection reliability, a substrate having a silicon through-electrode with sufficient conductivity and excellent connection reliability, and a copper paste for forming the silicon through-electrode are provided.
[0048] According to the above method, a substrate with silicon through-electrodes with excellent airtightness and impermeability (the property that liquids do not penetrate) can be provided. Attached Figure Description
[0049] Figure 1 This is a schematic diagram illustrating a method for manufacturing a substrate having a silicon through-electrode according to the first embodiment.
[0050] Figure 2 This is a schematic diagram illustrating a method for manufacturing a substrate having a silicon through-electrode according to the first embodiment.
[0051] Figure 3 This is a schematic diagram illustrating a method for manufacturing a substrate having a silicon through-electrode according to the first embodiment.
[0052] Figure 4 This is a schematic diagram illustrating the manufacturing method of the substrate having a silicon through-electrode according to the first embodiment and the substrate having a silicon through-electrode according to the first embodiment.
[0053] Figure 5 This is a schematic diagram illustrating the semiconductor device according to the first embodiment.
[0054] Figure 6 This is a schematic diagram illustrating a method for manufacturing a substrate having a silicon through-electrode according to the second embodiment.
[0055] Figure 7 This is a schematic diagram illustrating the manufacturing method of the substrate having a silicon through-electrode according to the second embodiment and the substrate having a silicon through-electrode according to the second embodiment.
[0056] Figure 8 This is a schematic diagram illustrating the semiconductor device according to the second embodiment.
[0057] Figure 9 This is a cross-sectional photograph of a copper sintered body formed in a through hole of a substrate with a silicon through electrode obtained in Example 1.
[0058] Figure 10 This is a schematic diagram representing the test piece. Detailed Implementation
[0059] Hereinafter, embodiments for carrying out the present invention will be described in detail with reference to the accompanying drawings. The present invention is not limited to the following embodiments. Furthermore, in the drawings, the same or corresponding parts are labeled with the same symbols, and repeated descriptions are omitted.
[0060] (Method for manufacturing a substrate with a silicon through-electrode according to the first embodiment)
[0061] Figures 1-4This is a schematic diagram illustrating a method for manufacturing a substrate having a silicon through-electrode according to the first embodiment.
[0062] The manufacturing method of the substrate having a silicon through-hole electrode according to the first embodiment includes: a preparation step, which prepares a silicon substrate, the silicon substrate including a silicon wafer having through holes, the through holes being provided on two main surfaces.
[0063] The copper sintered body forming process forms a copper sintered body with a porous structure by at least filling the aforementioned through holes;
[0064] The resin impregnation process involves impregnating the above-mentioned copper sintered body with a curable resin composition;
[0065] In the resin curing process, the curable resin composition impregnated in the copper sintered body is cured to form a conductor comprising the copper sintered body with pores filled with the cured resin, and a silicon through-hole electrode is provided in the through-hole.
[0066] <Preparation process for silicon substrate>
[0067] like Figure 1 As shown in (a), this process can prepare a silicon substrate 40, which has: a silicon wafer 1 having a through hole 30; and a metal coating 2 disposed on the wall of the through hole and the surface of the silicon wafer 1. The through hole 30 extends through both main surfaces of the silicon substrate 40.
[0068] From the viewpoint of suppressing substrate warping after sintering, the thickness of silicon wafer 1 can be 100μm or more, 200μm or more, or 300μm or more. From the viewpoint of reducing the weight / density of the substrate, it can be 800μm or less, 300μm or less, 200μm or less, or 100μm or less.
[0069] From the viewpoint of achieving high density of the obtained semiconductor device, the upper limit of the aperture of the through hole 30 can be less than 200 μm, less than 100 μm, or less than 60 μm, while the lower limit of the aperture of the through hole 30 is not particularly limited, but can be more than 20 μm or more than 50 μm.
[0070] From the viewpoint of achieving high density in the obtained semiconductor device, the number of through holes 30 provided on the silicon substrate 40 is approximately 1 cm. 2 The main surface of the substrate has more than 100 or more than 300.
[0071] The metal coating 2 can be disposed on both main surfaces of the silicon wafer 1 and the wall surface of the through-hole 30, or it can be disposed on at least one main surface of the silicon wafer 1 and the wall surface of the through-hole 30, or it can be disposed only on the wall surface of the through-hole 30, or it can be omitted. Figure 1 In the embodiment shown in (a), the silicon substrate 40 has a metal coating 2 on the two main surfaces of the silicon wafer 1 and on the wall surface of the through hole 30.
[0072] Examples of metal coatings 2 include titanium, nickel, chromium, copper, aluminum, palladium, platinum, and gold. From the viewpoint of adhesion, the metal coating 2 is preferably formed by sequentially stacking titanium, nickel, and copper. The surface of the silicon wafer 1 is oxidized to form silicon oxide, and a titanium layer is formed on the silicon oxide, thereby improving adhesion. Furthermore, a nickel layer is formed on the titanium layer, and a copper layer is formed on top of that, which, compared to the case where a copper layer is directly formed on the titanium layer, suppresses the diffusion of copper into the silicon wafer 1. In addition, by forming a copper layer on the surface, the adhesion between the copper sintered body formed in the copper sintered body formation process (described later) and the silicon substrate 40 is improved.
[0073] <Copper Sintering Body Formation Process>
[0074] In this process, a copper sintered body with a porous structure is formed in such a way that at least the through-holes are filled. In this embodiment, the copper sintered body is formed in such a way that it covers at least a portion of the main surface of the silicon substrate 40. In this case, a conductor that fills the through-holes of the silicon substrate 40 can be formed, and a conductor is also provided on the main surface of the silicon substrate 40. The conductor provided on the main surface of the silicon substrate 40 can form wiring and silicon through-electrodes.
[0075] The copper sintered body formation process may include: a copper paste filling process, in which copper paste containing copper particles is filled into through-holes of a silicon substrate; and a copper paste firing process, in which the copper paste is fired to form the copper sintered body. When the copper sintered body is formed on the main surface of the silicon substrate, copper paste layers may also be formed on both main surfaces of the silicon substrate during or after the copper paste filling process.
[0076] As a copper sintered body forming process as described above, for example, Figure 1 As shown in (b), copper paste 3 containing copper particles is applied to the silicon substrate 40, and the copper paste 3 fills the through holes 30. Copper paste 3 layers can also be formed on both main surfaces of the silicon substrate 40. Details about copper paste 3 will be described later.
[0077] Methods for applying copper paste 3 onto the silicon substrate 40 include, for example, screen printing, transfer printing, offset printing, jet printing, dispensers, jet dispensers, needle dispensers, comma-type coating machines, slot coating machines, stencil coating machines, photogravure coating machines, slot coating, letterpress printing, gravure printing, photogravure printing, stencil printing, flexographic printing, rod coating, applicator, particle deposition, spray coating machines, spin coating machines, dip coating machines, etc.
[0078] When copper paste is also applied to the main surface of the silicon substrate, the thickness of the copper paste layer can be 1μm or more, 2μm or more, 3μm or more, 5μm or more, 10μm or more, 15μm or more, or 20μm or more, or less than 300μm, 250μm or less, 200μm or less, 150μm or less, 120μm or less, 100μm or less, 80μm or less, or 50μm or less.
[0079] From the viewpoint of suppressing the flow of copper particles during the sintering of copper paste 3 or the generation of pores in the copper sintered body, copper paste 3 can be appropriately dried. When drying copper paste 3, the drying environment can be an oxygen-free environment such as nitrogen and rare gases, or a reducing environment such as hydrogen and formic acid.
[0080] Drying methods can include drying at room temperature, heating drying, and vacuum drying. Heating or vacuum drying can utilize devices such as hot plates, warm air dryers, warm air furnaces, nitrogen dryers, infrared dryers, infrared furnaces, far-infrared furnaces, microwave heating devices, laser heating devices, electromagnetic heating devices, heaters, steam furnaces, and hot plate pressing devices. The drying temperature and time can be adjusted appropriately based on the type and amount of dispersion medium used. Drying temperatures can range from above 50°C to below 180°C. Drying times can range from more than 1 minute to less than 120 minutes.
[0081] Following the copper paste filling process, the copper particles contained in copper paste 3 are sintered by firing copper paste 3. Thus, as... Figure 2 As shown in (c), a copper sintered body filled silicon substrate 50 is obtained, comprising a porous structure 4 and a copper sintered body 5 filling the through-holes 30. In this embodiment, a copper sintered body filled silicon substrate 50 is obtained in which copper sintered bodies 5 are also provided on both main surfaces of the silicon substrate 40. Details regarding the formed copper sintered bodies 5 will be described later.
[0082] It can be fired through heat treatment. In the heat treatment, heating methods such as hot plates, warm air dryers, warm air furnaces, nitrogen dryers, infrared dryers, infrared furnaces, far-infrared furnaces, microwave heating devices, laser heating devices, electromagnetic heating devices, heaters, and steam furnaces can be used.
[0083] From the viewpoint of suppressing oxidation of the copper sintered body, the firing environment is preferably an oxygen-free environment, and from the viewpoint of removing surface oxides from copper particles in the copper paste 3, a reducing environment is more preferred. Examples of an oxygen-free environment include the introduction of oxygen-free gases such as nitrogen or rare gases, or a vacuum environment. Examples of a reducing environment include pure hydrogen, a mixture of hydrogen and nitrogen (represented by synthesis gas), nitrogen containing formic acid, a mixture of hydrogen and rare gases, and a rare gas containing formic acid. As will be described later, when sintering the copper paste 3 by heating without pressurization, pure hydrogen or a mixture of hydrogen and nitrogen (represented by synthesis gas) is preferred, and pure hydrogen is more preferred. Heating in pure hydrogen lowers the sintering temperature of the copper particles. If pure hydrogen is used, even with a substrate thickness of up to 600 μm, the gas reaches the center of the through-hole 30, which has a small diameter of 10 μm, making it easy to obtain the copper sintered body 5.
[0084] From the perspective of reducing thermal damage to components and improving yield, the maximum temperature reached during heat treatment can be above 150°C, or below 350°C, 300°C, or 260°C. If the maximum temperature is above 150°C, sintering tends to proceed fully when the holding time at the maximum temperature is less than 60 minutes. From the perspective of ensuring complete volatilization of the dispersion medium and improving yield, the holding time at the maximum temperature can be more than 1 minute, or less than 60 minutes, 40 minutes, or 30 minutes.
[0085] Copper paste can be sintered under pressure. In this case, in an environment containing pure hydrogen, the pressure can be 0.05 MPa or more, 0.1 MPa or more, or 0.3 MPa, or 20 MPa or less, 15 MPa or less, or 10 MPa or less. Furthermore, in an environment containing nitrogen, the pressure can be 1 MPa or more, or 3 MPa, or 20 MPa or less, 15 MPa or less, or 10 MPa or less.
[0086] When using pure hydrogen, setting the pressure to 0.05 MPa or higher, and when using nitrogen, setting the pressure to 1 MPa or higher, easily suppresses the formation of porosity in the copper sintered body 5 formed in the center of the through-hole 30, thus easily obtaining a copper sintered body with good conductivity. Furthermore, by setting the pressure to the aforementioned lower limit or higher, when the silicon substrate 40 has a metal coating 2, it is easy to improve the bonding strength between the metal coating 2 and the copper sintered body 5. In addition, as... Figure 1 As shown in (b), when a silicon substrate 40 with a copper paste layer is clamped in from above and below by a pressure clamp A and pressure is applied, by setting the pressure applied to the pressure clamp A to a value above the aforementioned lower limit, the surface of the copper sintered body formed on the main surface of the silicon substrate 40 can be easily smoothed. If the surface of the copper sintered body is smooth, it has the advantage of easily forming fine wiring when forming wiring by etching or the like in subsequent processes. The pressure clamp A is not particularly limited and can be commercially available or made using metal parts with flat portions. For example, a pressure clamp having two or more of the aforementioned metal parts clamps the silicon substrate between metal parts arranged with their flat portions facing each other, thereby applying pressure to the silicon substrate. The pressure clamp A has a mechanism for adjusting the pressure applied to the silicon substrate. As a pressure adjustment method, a spring or the like can be used.
[0087] If the pressure is below 20 MPa, warpage of the silicon substrate 40 is easily suppressed. The inventors deduce the reason for this effect as follows: First, it is believed that if the pressure is increased, the sintering density of the copper paste (especially the density on the side in contact with the pressure fixture A) increases, and the thermal expansion coefficient of the resulting copper sintered body is close to the thermal expansion coefficient of ordinary copper at 25°C, which is 16.5 μm / (m·K). On the other hand, the thermal expansion coefficient of silicon at 25°C is 2.6 μm / (m·K). Therefore, it is believed that as the density of the copper sintered body increases, the difference in thermal expansion coefficients between the copper sintered body and silicon increases, making warpage more likely. In this embodiment, it is believed that by setting the pressure to below 20 MPa, the increase in the density of the copper sintered body is appropriately suppressed, resulting in a smaller difference in thermal expansion coefficients between the copper sintered body and silicon, thus suppressing warpage.
[0088] Furthermore, if the pressure during firing is within the aforementioned range, no special pressurizing device is required, thus further improving porosity reduction, bonding strength, and connection reliability without compromising yield. Examples of methods for applying pressure to a silicon substrate coated with copper paste include, for instance, placing a counterweight, using a pressurizing device, or using a clamping fixture for pressurization.
[0089] From the viewpoint of reducing the volume resistivity of the copper sintered body, based on the overall volume of the porous structure including the copper sintered body, the porosity of the copper sintered body formed on the main surface of the silicon substrate can be 15% or less, 14% or less, 12% or less, or 9% or less. Furthermore, from the viewpoint of suppressing cracks and warping of the silicon substrate 40, the porosity of the copper sintered body 5 can be 1% or more, 3% or more, or 5% or more.
[0090] Because the copper sintered body formed on the main surface of the silicon substrate has the above-mentioned porous structure, it can reduce the thermal expansion coefficient, reduce the difference in thermal expansion coefficient with the silicon wafer, and suppress cracks or warping of the silicon substrate.
[0091] From the viewpoint of reducing the volume resistivity of the copper sintered body, based on the overall volume of the porous structure including the copper sintered body, the porosity of the copper sintered body filling the through-holes can be 15% or less, 14% or less, 12% or less, or 9% or less. Furthermore, from the viewpoint of mitigating the stress applied to the copper sintered body to suppress cracking and warping of the silicon substrate, the porosity of the copper sintered body 5 can be 1% or more, 3% or more, or 5% or more.
[0092] Because the copper sintered body filling the through-hole has the aforementioned porous structure, the stress applied to the copper sintered body is mitigated, thereby suppressing cracking and warping of the silicon substrate.
[0093] In addition, the porosity of the copper sintered body is calculated in the following order.
[0094] (i) The cross section (the thickness direction of the substrate) of the copper sintered body filling the silicon substrate is exposed by focusing an ion beam.
[0095] (ii) Take cross-sectional images of the exposed section using a scanning electron microscope (within a range of 10 μm in the thickness direction of the substrate and within a range of 10 μm in the direction orthogonal to the thickness direction of the substrate).
[0096] (iii) The obtained cross-sectional image is binarized to separate the sintered copper portion from the porous portion.
[0097] (iv) From the binarized cross-sectional image, the ratio of the area of the porous portion to the total area of the copper sintered body cross section is set as the porosity of the copper sintered body.
[0098] In calculating the porosity of the copper sintered body filling the through-hole, in step (i) above, the cross-section of the central portion of the copper sintered body filling the through-hole is exposed. When calculating the porosity of the central portion of the copper sintered body filling the through-hole, the range of ±5 μm in the thickness direction of the substrate and the range of ±5 μm in the direction orthogonal to the thickness direction of the substrate are observed from the central portion of the copper sintered body filling the through-hole. In calculating the porosity of the copper sintered body formed on the main surface of the copper sintered body filling the silicon substrate, in step (i) above, the cross-section of the copper sintered body on the main surface is exposed. When calculating the porosity of the copper sintered body formed on the main surface of the copper sintered body filling the silicon substrate, the region from the surface of the copper sintered body formed on the main surface to 5 μm is observed.
[0099] When calculating the porosity of the copper sintered body used to calculate the filling rate of the resin cured material in the conductor described later, the observation site of the copper sintered body can be appropriately set to the same location as the observation site of the conductor.
[0100] Furthermore, if the pressure during firing is within the aforementioned range, no special pressurizing device is required, thus further improving porosity reduction, bonding strength, and connection reliability without compromising yield. Examples of methods for applying pressure to a silicon substrate coated with copper paste include, for instance, placing a counterweight, using a pressurizing device, or using a clamping fixture for pressurization.
[0101] Regarding copper sintered bodies, the proportion of copper in the constituent elements other than light elements can be 95% by mass or more, 97% by mass or more, 98% by mass or more, or even 100% by mass. If the proportion of copper in the copper sintered body is within the above range, the formation of intermetallic compounds or the precipitation of different types of elements into the copper grain boundaries can be suppressed, the properties of the copper constituting the copper sintered body are easily strengthened, and better connection reliability can be obtained.
[0102] In the copper sintering process, heating and firing can be performed without applying pressure to the copper paste. In this case, the porosity of the copper sintered body formed on the main surface of the silicon substrate tends to increase, and by reducing the thermal expansion coefficient of the copper sintered body, cracks or warping of the silicon substrate are less likely to occur.
[0103] <Resin Impregnation Process>
[0104] In this process, for example, by coating a curable resin composition onto a copper sintered body filled with a silicon substrate 50 obtained through a copper sintered body formation process, the curable resin composition can be impregnated in the copper sintered body 5. In this embodiment, the curable resin composition is impregnated in the copper sintered body 5 filling the through holes 30 and in the copper sintered body 5 formed on the two main surfaces of the silicon substrate 40. Furthermore, it is preferable that the pores 4 of the copper sintered body 5 are sufficiently filled by the impregnated curable resin composition.
[0105] (Curing resin composition)
[0106] Examples of thermosetting compounds that constitute a curable resin composition include oxobutane compounds, epoxy compounds, cyclic sulfur compounds, (meth)acrylic acid compounds, phenolic compounds, amino compounds, unsaturated polyester compounds, polyurethane compounds, silicone compounds, and polyimide compounds. Among these, epoxy compounds are particularly suitable for further optimizing the curability and viscosity of the curable resin composition, improving its properties during high-temperature storage, or enhancing its insulation reliability.
[0107] The curable resin composition may also contain a thermosetting agent. Examples of thermosetting agents include imidazole curing agents, amine curing agents, phenol curing agents, polythiol curing agents, acid anhydrides, thermal cationic initiators, and thermal free radical generators. These can be used alone or in combination of two or more. From the perspective of rapid curing at low temperatures, imidazole curing agents, polythiol curing agents, or amine curing agents are preferred. Furthermore, when a thermosetting compound and a thermosetting agent are mixed, a latent curing agent is preferred from the viewpoint of improved storage stability. The latent curing agent is preferably a latent imidazole curing agent, a latent polythiol curing agent, or a latent amine curing agent. Additionally, the aforementioned thermosetting agents can be coated with a polymer such as polyurethane resin or polyester resin.
[0108] The imidazole curing agent is not particularly limited and can include 2-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-phenylimidazole tricarboxylate, 2,4-diamino-6-[2'-methylimidazole-(1')]-ethyl-triazine, and 2,4-diamino-6-[2'-methylimidazole-(1')]-ethyl-triazine isocyanuric acid adducts, etc.
[0109] The polythiol curing agent is not particularly limited, and examples include trimethylolpropane tri-3-mercaptopropionate, pentaerythritol tetra-3-mercaptopropionate, and dipentaerythritol hexa-3-mercaptopropionate. The solubility parameter of the polythiol curing agent is preferably 9.5 or higher, and more preferably 12 or lower. The solubility parameter is calculated using the Fedor's method. For example, the solubility parameter of trimethylolpropane tri-3-mercaptopropionate is 9.6, and the solubility parameter of dipentaerythritol hexa-3-mercaptopropionate is 11.4.
[0110] The above-mentioned amine curing agents are not particularly limited, and examples include hexamethylenediamine, octamethylenediamine, decamethylenediamine, 3,9-bis(3-aminopropyl)-2,4,8,10-tetraspiro[5.5]undecane, bis(4-aminocyclohexyl)methane, m-phenylenediamine, and diaminodiphenyl sulfone.
[0111] Examples of the aforementioned cationic curing agents include iodonium-based cationic curing agents, oxonium-based cationic curing agents, and sulfonium-based cationic curing agents. Examples of iodonium-based cationic curing agents include bis(4-tert-butylphenyl)hexafluorophosphate. Examples of oxonium-based cationic curing agents include trimethyloxonium tetrafluoroborate. Examples of sulfonium-based cationic curing agents include tri-o-toluenesulfonium hexafluorophosphate.
[0112] The aforementioned thermal free radical generators are not particularly limited, and examples include azo compounds and organic peroxides. Examples of azo compounds include azobisisobutyronitrile (AIBN). Examples of organic peroxides include di-tert-butyl peroxide and methyl ethyl ketone peroxide.
[0113] Methods for coating curable resin compositions include screen printing, transfer printing, offset printing, jet printing, dispensers, jet dispensers, needle dispensers, comma-type coaters, slot coaters, stencil coaters, photogravure coaters, slot coating, letterpress printing, gravure printing, photogravure printing, stencil printing, flexographic printing, rod coating, applicator, particle deposition, spraying machines, spin coaters, dip coaters, etc.
[0114] The curable resin composition can be applied to one main surface of the copper sintered silicon substrate 50, or to a portion of the main surface. When applying the resin composition to both surfaces of the copper sintered silicon substrate 50, the resin composition can be applied to one main surface of the copper sintered silicon substrate 50, allowing the resin composition to penetrate to the uncoated main surface of the copper sintered silicon substrate 50, and then applied to the uncoated main surface. This allows the resin composition to permeate the porous structure 4.
[0115] By placing the copper sintered body filled silicon substrate 50 coated with a curable resin composition under a reduced pressure environment, the impregnation of the curable resin composition into the porous structure 4 of the copper sintered body 5 can be improved.
[0116] In the resin impregnation process, it is preferable to impregnate the copper sintered body with the cured resin composition in such a way that the filling rate of the cured resin in the conductor formed by the resin curing process is within the preferred range described later.
[0117] <Resin Curing Process>
[0118] In this process, such as Figure 2 As shown in (d), by curing the curable resin composition (curable resin composition filled into the porous 4) impregnated in the copper sintered body 5, a conductive body 35 comprising a copper sintered body 5 with resin cured material 6 filled in the porous 4 is formed, and a substrate 51 having silicon through electrodes provided in the through holes 30 can be obtained. In this embodiment, the conductive body 35 comprising a copper sintered body 5 with resin cured material 6 filled in the porous 4 is also provided on both main surfaces of the silicon substrate 40.
[0119] The curing of the curable resin composition can be carried out by heat treatment. Heat treatment can be performed using heating methods such as hot plates, warm air dryers, warm air furnaces, nitrogen dryers, infrared dryers, infrared furnaces, far-infrared furnaces, microwave heating devices, laser heating devices, electromagnetic heating devices, heaters, and steam furnaces.
[0120] From the perspective of suppressing the oxidation of the copper sintered body 5, the environment in the resin curing process can be an oxygen-free environment; from the perspective of removing surface oxides from the copper sintered body 5, it can be a reducing environment. Examples of an oxygen-free environment include the introduction of oxygen-free gases such as nitrogen or rare gases, or a vacuum environment. Examples of a reducing environment include pure hydrogen, a mixture of hydrogen and nitrogen (represented by synthesis gas), nitrogen containing formic acid, a mixture of hydrogen and rare gases, and rare gases containing formic acid.
[0121] From the perspective of reducing thermal damage to various components and improving yield, the maximum temperature reached during the heat treatment in the resin curing process can be above 150°C, or below 350°C, 300°C, or 260°C. If the maximum temperature is above 150°C, the resin composition tends to cure sufficiently if the holding time at the maximum temperature is less than 60 minutes.
[0122] In the conductor 35 (conductor before the conductor removal process) formed in the resin curing process, the filling rate of the cured resin 6 can meet the following conditions.
[0123] (Conductor in a through-hole)
[0124] (a) In the region from the point S1 where the line L1 extending in the thickness direction of the substrate through the central portion C (the center of the hole length and the center of the hole diameter) of the through hole 30 intersects the surface of the conductor 35 to a depth of 10 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the porous internal space of the copper sintered body.
[0125] (b) In the region from point S1 to a depth of 10 to 20 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0126] (c) In the region from point S1 to a depth of 20 to 30 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0127] (d) Based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, within a range of ±5μm in the thickness direction of the substrate and within a range of ±5μm in the direction orthogonal to the thickness direction of the substrate.
[0128] (Conductors on the main surface of the substrate)
[0129] (e) In the region from the surface S2 of the conductor 35 formed on the main surface of the substrate to a depth of 5 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total internal space volume of the porous 4 of the copper sintered body 5.
[0130] (f) In the region from the surface S2 of the conductor 35 formed on the main surface of the substrate to a depth of 10 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total internal space volume of the porous 4 of the copper sintered body 5.
[0131] (g) In the region from the surface S2 to a depth of 10 to 20 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0132] (h) In the region from the surface S2 to a depth of 20 to 30 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0133] The filling rate of the resin cured material 6 in the conductor 35 is calculated in the following order.
[0134] (i) The cross section (the cross section in the thickness direction of the substrate) of the conductor filling the silicon substrate is exposed by focusing an ion beam.
[0135] (ii) Take cross-sectional images of the exposed section using a scanning electron microscope (within a range of 10 μm in the thickness direction of the substrate and within a range of 10 μm in the direction orthogonal to the thickness direction of the substrate). (iii) Perform binarization on the obtained cross-sectional images to separate the sintered copper portion and the resin-cured portion from the porous portion not filled by the resin-cured portion.
[0136] (iv) From the binarized cross-sectional image, determine the ratio of the area of the porous portion not filled by the resin curing material to the total area of the conductor cross-section, and set it as the porosity of the conductor.
[0137] (v) Substitute the porosity of the copper sintered body before impregnation with the curing resin composition and the porosity of the conductor into the following formula (1) to calculate the filling rate of the resin curing in the conductor.
[0138] The filling rate (%) of the cured resin in the conductor = [(BA) / B] × 100……Equation (1)
[0139] [In formula (1), A represents the porosity (%) of the conductor, and B represents the porosity (%) of the copper sintered body.]
[0140] When calculating the porosity of the conductor filling the through-hole, in (i) above, the cross-section of the central portion of the conductor within the through-hole is exposed. When calculating the porosity of the conductor formed on the main surface of the conductor-filled silicon substrate, in (i) above, the cross-section of the conductor on the main surface is exposed.
[0141] <Conductor Removal Process>
[0142] In this process, at least a portion of the conductor 35 formed on the main surface of the silicon substrate 40 can be removed. Methods for removing the conductor include chemical polishing, mechanical polishing, chemical mechanical polishing, fly cutting, and plasma treatment. Fly cutting implies planarization based on a planer.
[0143] In this embodiment, as a general method, from the viewpoint of being simple and applicable, the removal method is preferably selected from one or more of the group consisting of etching, mechanical polishing and chemical mechanical polishing, but is not limited thereto.
[0144] The method for manufacturing a silicon substrate with a silicon through-electrode in this embodiment includes a conductor removal process, which makes the surface of the conductor 35 formed on the main surface of the silicon substrate 40 flat and facilitates wiring.
[0145] In this embodiment, the filling rate of the cured resin 6 in the conductor 35 after the conductor removal process can meet the following conditions. Furthermore, the filling rate can be calculated in the same manner as described above.
[0146] (Conductor in a through-hole)
[0147] (a) In the region from the point S3 where the line L1 extending from the center C of the through hole 30 (the center of the hole length and the center of the hole diameter D) in the thickness direction of the substrate intersects the surface of the conductor 35 to a depth of 10 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the porous internal space of the copper sintered body.
[0148] (b) In the region from point S3 to a depth of 10 to 20 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0149] (c) In the region from point S3 to a depth of 20 to 30 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0150] (d) Based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, within a range of ±5μm in the thickness direction of the substrate and within a range of ±5μm in the direction orthogonal to the thickness direction of the substrate.
[0151] (Conductors on the main surface of the substrate)
[0152] (e) In the region from the surface S4 of the conductor 35 formed on the main surface of the substrate to a depth of 5 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total internal space volume of the porous 4 of the copper sintered body 5.
[0153] (f) In the region from the surface S4 of the conductor 35 formed on the main surface of the substrate to a depth of 10 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total internal space volume of the porous 4 of the copper sintered body 5.
[0154] (g) In the region from the surface S4 to a depth of 10 to 20 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0155] (h) In the region from the surface S4 to a depth of 20 to 30 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0156] From the viewpoint of achieving high density in the obtained semiconductor device, the ratio L / D of the length L of the silicon through-electrode can be 1 or more, 5 or more, or 10 or more, or it can be 15 or less, 10 or less, or 5 or less. The length L of the silicon through-electrode can be set as the thickness of the substrate having the silicon through-electrode. In this case, the ratio T / D of the thickness T of the substrate having the silicon through-electrode to the aperture D of the silicon through-electrode can be within the above-mentioned range.
[0157] The method for manufacturing a substrate with a silicon through-electrode in this embodiment may further include a wiring formation step. The wiring formation step may include a resist formation step, an etching step, and a resist removal step as described below.
[0158] <Resist Forming Process>
[0159] In the resist forming process, such as Figure 3 As shown in (f), an etch resist 8 is formed on a conductor 35 formed on the main surface of a silicon substrate 40.
[0160] Methods for forming the etching resist 8 include, for example, screen printing the resist ink, or laminating the etching resist onto a copper foil using a negative photosensitive dry film, overlapping it with a photomask that transmits light in a wire-like shape, exposing it with ultraviolet light, and removing the unexposed areas with a developer.
[0161] <Etching Process>
[0162] In the etching process, such as Figure 4 As shown in (g), the portion of the conductor 35 not covered by the etch resist 8 is removed by etching. In this embodiment, a portion of the metal coating 2 disposed on the two main surfaces of the silicon wafer 1 is removed by etching.
[0163] Examples of etching methods include chemical etching solutions used in ordinary wiring boards, such as solutions of copper chloride and hydrochloric acid, ferric chloride, sulfuric acid and hydrogen peroxide, and ammonium persulfate.
[0164] <Resist Removal Process>
[0165] In the resist removal process, the etch resist 8 formed on the conductor 35 is removed.
[0166] The method for manufacturing a substrate with a silicon through-electrode according to this embodiment also includes a wiring formation step having the above-described steps, thus enabling the formation of wiring 9 including a conductor 35 on the main surface of the silicon substrate 40.
[0167] (The substrate with a silicon through-electrode according to the first embodiment)
[0168] Figure 4 (h) is a cross-sectional view of an embodiment of a substrate having a silicon through electrode that can be manufactured by the method described in the first embodiment above. Figure 4 The substrate 52 with silicon through-hole electrodes shown in (h) includes a silicon wafer 1 with through-holes 30 and a silicon substrate 40 with through-holes 30 through two main surfaces and a conductor 35 filling the through-holes 30. The conductor 35 includes a copper sintered body 5 with a porous structure and a resin cured material 6 filled into the pores 4 of the copper sintered body 5.
[0169] Figure 4 (h) The substrate 52 with silicon through-hole electrodes shown has a metal coating 2 on the two main surfaces of the silicon wafer 1 and on the wall of the through-hole. However, the metal coating 2 may not be provided on the main surfaces, may be provided on only one main surface, or may not be provided on the wall of the through-hole. Furthermore, the substrate 52 with silicon through-hole electrodes has wiring 9, which includes the metal coating 2 and the conductor 35, provided on the two main surfaces of the silicon substrate 40. However, the wiring 9 may also be provided on only one main surface of the silicon substrate 40.
[0170] In the substrate 52 having a silicon through-electrode, the filling rate of the resin cured material 6 in the conductor 35 can satisfy the following conditions. Furthermore, the filling rate can be calculated in the same manner as described above.
[0171] (Conductor in a through-hole)
[0172] (a) In the region from the point S5 where the line L1 extending in the thickness direction of the substrate through the central portion C of the through hole 30 (the center of the hole length and the center of the hole diameter) intersects the surface of the conductor 35 to a depth of 10 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the porous internal space of the copper sintered body.
[0173] (b) In the region from point S5 to a depth of 10 to 20 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0174] (c) In the region from point S5 to a depth of 20 to 30 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0175] (d) Based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, within a range of ±5μm in the thickness direction of the substrate and within a range of ±5μm in the direction orthogonal to the thickness direction of the substrate.
[0176] (Conductors on the main surface of the substrate)
[0177] (e) In the region from the surface S6 of the conductor 35 formed on the main surface of the substrate to a depth of 5 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the internal space of the porous 4 of the copper sintered body 5.
[0178] (f) In the region from the surface S6 of the conductor 35 formed on the main surface of the substrate to a depth of 10 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the internal space of the porous 4 of the copper sintered body 5.
[0179] (g) In the region from the surface S6 to a depth of 10 to 20 μm, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more, based on the total volume of the porous internal space of the copper sintered body.
[0180] (h) In the region from the surface S6 to a depth of 20 to 30 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0181] (Semiconductor device according to the first embodiment)
[0182] Regarding semiconductor devices manufactured using the substrate with silicon through-electrodes according to the first embodiment, using Figure 5 To explain in detail. Figure 5 This is a schematic cross-sectional view illustrating one embodiment of the semiconductor device of the present invention. Figure 5 In the semiconductor device 100 shown in (a), the wiring 27 on the interposer substrate 25 is directly connected to the conductor 35 of the substrate 51 having a silicon through-electrode, thereby enabling flip-chip bonding between the interposer substrate 25 and the substrate 51 having the silicon through-electrode. The gap between the interposer substrate 25 and the substrate 51 having the silicon through-electrode is filled seamlessly with a cured adhesive 20 and sealed. On the main surface of the substrate 51 having the silicon through-electrode, opposite to the interposer substrate 25, the substrate 51 having the silicon through-electrode is repeatedly stacked. The substrates 51 having the silicon through-electrode are connected to each other by the conductor 35. The gaps between the substrates 51 having the silicon through-electrode are filled seamlessly with a cured adhesive 20 and sealed.
[0183] The semiconductor device 100 can be obtained, for example, by the following method: A substrate 51 having a silicon through electrode is laminated with an adhesive to obtain a laminate. The adhesive can be cured during lamination. The obtained laminate is electrically connected to an intercalation substrate 25 by pressing, forming a connector that electrically connects the laminate and the intercalation substrate 25. Cutting tape is adhered to the side of the formed connector opposite to the side on which the intercalation substrate 25 is disposed, and the connector is cut along the cutting line, thereby obtaining the semiconductor device 100.
[0184] exist Figure 5 In the semiconductor device 200 shown in (b), wiring 27 on the interposer substrate 25 is connected to the conductor 35 of the substrate 51 with silicon through-electrodes via microbumps 15, thereby enabling flip-chip bonding between the interposer substrate 25 and the substrate 51 with silicon through-electrodes. The gaps between the interposer substrate 25 and the substrate 51 with silicon through-electrodes are filled seamlessly with cured adhesive 20 and sealed. On the main surface of the substrate 51 with silicon through-electrodes on the side opposite to the interposer substrate 25, substrates 51 with silicon through-electrodes are repeatedly stacked via microbumps 15. The gaps between the substrates 51 with silicon through-electrodes are filled seamlessly with cured adhesive 20 and sealed.
[0185] The semiconductor device 200 can be obtained, for example, by the following method: A substrate 51 with silicon through-electrodes having micro-bumps 15 on one main surface is laminated with an adhesive to obtain a laminate. The adhesive can be cured during lamination. The obtained laminate is electrically connected to an intercalation substrate 25 by pressing, forming a connector that electrically connects the laminate and the intercalation substrate 25. Cutting tape is adhered to the side of the formed connector opposite to the side where the intercalation substrate 25 is provided, and the connector is cut along the cutting line, thereby obtaining the semiconductor device 200.
[0186] (Method for manufacturing a substrate with a silicon through-electrode according to the second embodiment)
[0187] Figure 6 and Figure 7 This is a schematic diagram illustrating a method for manufacturing a substrate having a silicon through-electrode according to the second embodiment.
[0188] The manufacturing method of the substrate having a silicon through-hole according to the second embodiment includes: a preparation step, preparing a silicon substrate, the silicon substrate including a silicon wafer having a non-through-hole, and the non-through-hole being opened on a main surface.
[0189] The copper sintered body forming process forms a copper sintered body with a porous structure by at least filling the aforementioned non-penetrating holes.
[0190] The resin impregnation process involves impregnating the above-mentioned copper sintered body with a curable resin composition;
[0191] The resin curing process involves curing the curable resin composition impregnated in the copper sintered body to form a conductive body comprising the copper sintered body with porous structures filled with cured resin; and
[0192] In the grinding process, a silicon through electrode is provided by grinding the side of the silicon substrate on which the above-mentioned conductive material is formed, opposite to the side with the above-mentioned non-through hole.
[0193] <Preparation process for silicon substrate>
[0194] like Figure 6 As shown in (a), in this process, a silicon substrate 41 is prepared. The silicon substrate 41 has: a silicon wafer 1 having a non-through-hole 31; and a metal coating 2 disposed on the wall and bottom surfaces of the non-through-hole 31 and the surface of the silicon wafer 1. The non-through-hole 31 opens on one main surface of the silicon wafer 1.
[0195] From the viewpoint of suppressing substrate warping after sintering, the thickness of silicon wafer 1 can be 20μm or more, 30μm or more, or 50μm or more, or it can be less than 500μm, less than 400μm or less, or less than 300μm.
[0196] From the viewpoint of achieving high density of the obtained semiconductor device, the upper limit of the aperture of the non-through hole 31 can be less than 200μm, less than 100μm, or less than 60μm, while the lower limit of the aperture of the non-through hole 31 is not particularly limited and can be more than 10μm or more than 30μm.
[0197] The length (depth) of the non-penetrating hole 31 can be appropriately set according to the length of the silicon through electrode formed.
[0198] The metal coating 2 can be disposed on the surface of the silicon wafer 1 where the opening has the non-through hole 31, the wall surface of the non-through hole 31, and the bottom surface; it can also be disposed on the wall surface of the non-through hole 31, or it can be omitted. Figure 6 In the embodiment shown in (a), the silicon substrate 41 has a metal coating 2 on the surface of the opening with the non-through hole 31 and the wall and bottom surfaces of the non-through hole 31 in the silicon wafer 1.
[0199] As the metal coating 2, the same material as in the first embodiment can be used.
[0200] <Copper Sintering Body Formation Process>
[0201] In this process, a copper sintered body with a porous structure is formed in such a way that at least the non-through holes are filled. In this embodiment, the copper sintered body is formed in such a way that at least a portion of the surface of the silicon substrate 41 with openings of non-through holes 31 is covered. In this case, a conductor is formed that fills the non-through holes 31 of the silicon substrate 41, and the conductor can also be provided on the surface of the silicon substrate 41 with openings of non-through holes 31.
[0202] The copper sintered body formation process may include: a copper paste filling process, in which copper paste containing copper particles is filled into non-through holes in a silicon substrate; and a copper paste firing process, in which the copper paste is fired to form the copper sintered body. When a copper sintered body is formed on a surface in the silicon substrate with openings of non-through holes, a copper paste layer may also be provided on the surface in the silicon substrate with openings of non-through holes during or after the copper paste filling process.
[0203] As a copper sintered body forming process as described above, for example, Figure 6 As shown in (b), copper paste 3 containing copper particles is applied to the silicon substrate 41, and the copper paste 3 fills the non-through-holes 31. A copper paste 3 layer can also be formed on the surface of the silicon substrate 41 where the non-through-holes 31 are located. Details regarding the copper paste 3 will be described later.
[0204] As a method for applying copper paste 3 onto silicon substrate 41, the same method as in the first embodiment can be cited.
[0205] When copper paste is also applied to the surface of the silicon substrate 41 where the opening is a non-through hole 31, from the viewpoint of suppressing the warping of the silicon substrate 41 and reducing the burden in the conductor removal process described later, the thickness of the copper paste layer can be less than 30 μm, less than 20 μm, less than 15 μm, or less than 10 μm.
[0206] The copper paste 3 can be dried appropriately in the same manner as in the first embodiment. When drying the copper paste 3, the drying environment, drying method, and drying temperature can be the same as in the first embodiment.
[0207] Following the copper paste filling process, the copper particles contained in copper paste 3 are sintered by firing copper paste 3. Thus, as... Figure 7 As shown in (c), a copper sintered body filled silicon substrate 60 is obtained in which a copper sintered body 5 having a porous structure, including a porous structure 4, is filled in the non-through hole 31. In this embodiment, a copper sintered body filled silicon substrate 60 is obtained in which the copper sintered body 5 is also provided on the surface of the silicon substrate 41 with the opening of the non-through hole 31.
[0208] The firing conditions can be the same as in the first embodiment.
[0209] The porosity of the copper sintered body formed on the surface of the silicon substrate with non-through holes can be the same as the porosity of the copper sintered body formed on the main surface of the silicon substrate in the first embodiment. The porosity of the copper sintered body can be calculated in the same order as in the first embodiment.
[0210] The porosity of the copper sintered body filling the non-through holes can be the same as the porosity of the copper sintered body filling the through holes in the first embodiment.
[0211] The proportion of copper in the constituent elements other than light elements in the copper sintered body can be the same as in the first embodiment.
[0212] <Resin Impregnation Process>
[0213] In this process, for example, a curable resin composition is coated onto the copper sintered body filled silicon substrate 60 obtained through the copper sintered body formation process, thereby enabling the curable resin composition to be impregnated in the copper sintered body 5. In this embodiment, the curable resin composition is impregnated in both the copper sintered body 5 filled with non-through holes 31 and the copper sintered body 5 formed on the surface of the silicon substrate 41 with openings of non-through holes. Furthermore, it is preferable that the pores 4 of the copper sintered body 5 are sufficiently filled by the impregnated curable resin composition.
[0214] As the curable resin composition, the same composition as in the first embodiment can be used. The coating method for the curable resin composition can be the same as in the first embodiment. The filling rate of the curable resin composition on the pores 4 of the copper sintered body 5 can be appropriately changed according to the filling rate of the cured resin product 6 of the conductor 35 after the resin curing process.
[0215] <Resin Curing Process>
[0216] In this process, a conductive body 35 is formed by curing a curable resin composition (a curable resin composition filled into the porous 4) impregnated in the copper sintered body 5 and curing it. This results in a copper sintered body 5 containing a cured resin 6 filling the porous 4. In this embodiment, a conductive body 35 containing a copper sintered body 5 containing a cured resin 6 filling the porous 4 is also provided on the surface of the silicon substrate 41 where the opening has a non-through hole.
[0217] The curing conditions of the resin composition in the resin curing process can be the same as those in the first embodiment.
[0218] The fill rate of the resin-cured material formed in the resin curing process (the conductor before the conductor removal process and the grinding process) can be adjusted so that the fill rate of the resin-cured material in the formed silicon through-electrode meets the conditions described later. For example, the fill rate of the resin-cured material in the conductor can satisfy the following conditions.
[0219] (Conductor without through-hole)
[0220] (a) In the region from the point where a line extending in the thickness direction of the substrate through the center of the non-through hole (the center of the hole length and the center of the hole diameter) intersects the surface of the conductor to a depth of 10 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the porous internal space of the copper sintered body.
[0221] (b) In the region from the point where the line extending in the thickness direction of the substrate through the center of the non-through hole intersects the surface of the conductor to a depth of 10 to 20 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the porous internal space of the copper sintered body.
[0222] (c) In the region from the point where the line extending in the thickness direction of the substrate through the center of the non-through hole intersects the surface of the conductor to a depth of 20 to 30 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the porous internal space of the copper sintered body.
[0223] (Conductors on the main surface of the substrate)
[0224] (e) In the region from the surface of the conductor formed on the main surface of the substrate to a depth of 5 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the porous internal space of the copper sintered body.
[0225] (f) In the region from the surface of the conductor formed on the main surface of the substrate to a depth of 10 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the porous internal space of the copper sintered body.
[0226] (g) In the region from the surface of the conductor formed on the main surface of the substrate to a depth of 10 to 20 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the porous internal space of the copper sintered body.
[0227] (h) In the region from the surface of the conductor formed on the main surface of the substrate to a depth of 20 to 30 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the porous internal space of the copper sintered body.
[0228] The filling rate of the resin cured material 6 in the conductor is calculated in the same manner as described in the manufacturing method of the substrate having a silicon through electrode according to the first embodiment.
[0229] <Conductor Removal Process>
[0230] The method for manufacturing a substrate with a silicon through-electrode in this embodiment may include a conductor removal step after the resin curing step. In this step, at least a portion of the conductor 35 formed on a main surface of the silicon substrate 41 can be removed. The method for removing the conductor can be the same as in the first embodiment.
[0231] <Grinding process>
[0232] In this process, such as Figure 7 As shown in (d), by grinding the side of the silicon substrate where the conductor 35 is formed, opposite to the side where the non-through hole 31 is initially formed, a substrate 61 having a silicon through electrode with a silicon electrode can be obtained. That is, in this process, by grinding, the conductor 35 is exposed on the side of the silicon substrate opposite to the side where the non-through hole 31 is opened, thereby forming a silicon through electrode. Figure 7 In (d), the conductor 35 formed on the surface of the silicon substrate with the opening of the non-through hole 31 is removed by the conductor removal process.
[0233] Examples of grinding methods include mechanical grinding and chemical mechanical grinding, but they are not limited to these.
[0234] In this embodiment, the filling rate of the cured resin 6 in the conductor 35 after the grinding process can meet the following conditions. Furthermore, the filling rate can be calculated in the same manner as described above.
[0235] (a) In the region from the point S21 where the line L2 extending from the center portion E (the center of the length L and the center of the aperture D) through the silicon through electrode and in the thickness direction of the substrate intersects the surface of the conductor 35 to a depth of 10 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the porous internal space of the copper sintered body.
[0236] (b) In the region from point S21 to a depth of 10 to 20 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0237] (c) In the region from point S21 to a depth of 20 to 30 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0238] (d) Based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, within a range of ±5μm in the thickness direction of the substrate and within a range of ±5μm in the direction orthogonal to the thickness direction of the substrate.
[0239] The ratio of the length L of the silicon through-electrode to the aperture D, L / D, can be the same as in the first embodiment.
[0240] (The substrate with a silicon through-electrode according to the second embodiment)
[0241] Figure 7 (d) is a cross-sectional view of an embodiment of a substrate having a silicon through electrode that can be manufactured by the method described in the second embodiment above. Figure 7 (d) shows a substrate 61 with a silicon through-hole electrode, which includes a silicon wafer 1 with through-holes and through-holes on two main surfaces, and a conductor 35 filling the through-holes. The conductor 35 includes a copper sintered body 5 with a porous structure and a resin cured material 6 filled into the pores 4 of the copper sintered body 5.
[0242] Figure 7 (d) shows a substrate 61 with a silicon through electrode where no conductor 35 is formed on either of the two main surfaces, but a conductor 35 may be formed on one of the main surfaces. Figure 7 (d) The substrate 61 with silicon through-hole shown has a metal coating 2 on the wall of the through-hole, but the metal coating 2 may not be provided on the wall of the through-hole.
[0243] The filling rate of the resin cured material 6 of the conductor 35 contained in the substrate 61 with silicon through-electrode can be the same as the filling rate of the resin cured material 6 in the conductor 35 after the grinding process.
[0244] (Semiconductor device according to the second embodiment)
[0245] Regarding semiconductor devices manufactured using the substrate with silicon through-electrodes according to the second embodiment, using Figure 8 To explain in detail. Figure 8 This is a schematic cross-sectional view illustrating one embodiment of the semiconductor device of the present invention. Figure 8 The semiconductor device 300 shown has a substrate 61 having silicon through electrodes stacked on top of each other. The substrates 61 having silicon through electrodes are electrically connected to each other.
[0246] In the semiconductor device 300, the filling rate of the resin cured material 6 in the conductor 35 can meet the following conditions. Furthermore, the filling rate can be calculated in the same manner as described above.
[0247] (Silicon through-electrode conductor)
[0248] (a) In the region from the point S22 where the line L2 extending from the central portion E (the center of the length L and the center of the aperture D) through the silicon through electrode and in the thickness direction of the substrate intersects the surface of the conductor 35 to a depth of 10 μm, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, based on the total volume of the porous internal space of the copper sintered body.
[0249] (b) In the region from point S22 to a depth of 10 to 20 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0250] (c) In the region from point S22 to a depth of 20 to 30 μm, based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured product can be 80% or more, 90% or more, or 95% or more.
[0251] (d) Based on the total volume of the porous internal space of the copper sintered body, the filling rate of the resin cured material can be 80% or more, 90% or more, or 95% or more, within a range of ±5μm in the thickness direction of the substrate and within a range of ±5μm in the direction orthogonal to the thickness direction of the substrate.
[0252] (copper paste)
[0253] The copper paste containing copper particles used in the manufacturing methods of the substrate having a silicon through-electrode according to the first and second embodiments will be described.
[0254] Copper paste may contain, for example, first copper particles with a particle size (maximum diameter) of 0.8 μm or larger as copper particles.
[0255] The particle size (maximum diameter) of the first copper particle can be greater than 1.2 μm. The particle size (maximum diameter) of the first copper particle can be less than 10 μm or less than 8.0 μm.
[0256] From the viewpoint of increasing the sintering density in the through holes to suppress the porosity generated in the through holes, the average particle size (average maximum diameter) of the first copper particles contained in the copper paste can be 0.5 μm or more, 0.8 μm or more, or 1.2 μm or more, or 20 μm or less, 10 μm or less, or 8 μm or less.
[0257] The particle size (maximum diameter) and average particle size (average maximum diameter) of the first copper particle can be determined, for example, from an SEM image of the particle. An example is given of a method for calculating the particle size (maximum diameter) of the first copper particle from an SEM image. The powder of the first copper particle is placed on a carbon ribbon for SEM using a scraper, and this is designated as the SEM sample. The SEM sample is observed using an SEM apparatus at 5000x magnification. A rectangle circumscribed around the first copper particle in the SEM image is drawn using image processing software, and the longer side of the rectangle is defined as the particle size (maximum diameter). This measurement is performed on more than 50 first copper particles using multiple SEM images, and the average particle size (average maximum diameter) is calculated.
[0258] The shape of the first copper particle can be, for example, spherical, blocky, needle-like, flat (flake-like), or roughly spherical. The first copper particle can be an aggregate of copper particles with these shapes.
[0259] The first copper particle is preferably flat (sheet-like) with an aspect ratio (length / diameter / thickness) of 4 or more. In this case, the first copper particle is oriented approximately parallel to the coating surface of the copper paste, thereby suppressing the volume shrinkage during sintering of the copper particles in the copper paste and easily suppressing porosity generated in the through holes. Furthermore, by suppressing the volume shrinkage during sintering of the copper particles in the copper paste, cracks in the copper sintered body formed on at least one main surface of the silicon substrate can be suppressed.
[0260] The aspect ratio of the first copper particle is preferably 4 or more, more preferably 5 or more, and even more preferably 6 or more. If the aspect ratio is within the above range, the first copper particle in the copper paste can easily be oriented parallel to the coating surface of the copper paste, which can suppress volume shrinkage during sintering of the copper particles in the copper paste. Therefore, when wiring is formed from a conductor provided on the main surface of the silicon substrate, wire breakage caused by thermal stress of the wiring can be further suppressed. Furthermore, the adhesion between the sintered copper body and the metal coating formed on the silicon wafer can be improved. The aspect ratio (length / diameter / thickness) of the copper particles in the copper paste can be determined, for example, by observing an SEM image of the particles and measuring the length, diameter, and thickness.
[0261] The copper paste preferably contains first copper particles with a particle size (maximum diameter) of 0.8 μm or more and 10 μm or less, and an aspect ratio of 4 or more. By including these first copper particles in the copper paste, the volume shrinkage during sintering of the copper particles in the copper paste can be significantly reduced, and a copper sintered body with a porous structure and a fully formed conductive network can be easily formed in through-holes or non-through-holes. As a result, the formation of porosity in through-holes or non-through-holes can be suppressed, and a copper sintered body that is less prone to cracking on the main surface of the silicon substrate can be formed. When wiring is formed from a conductor containing this copper sintered body, wire breakage caused by thermal stress of the wiring can be further suppressed.
[0262] The copper paste may contain copper particles with a particle size (maximum diameter) of 0.8 μm or more and 10 μm or less, and an aspect ratio of less than 2. However, the content of copper particles with a particle size (maximum diameter) of 0.8 μm or more and 10 μm or less, and an aspect ratio of less than 2, relative to 100 parts by mass of the first copper particles with a particle size (maximum diameter) of 0.8 μm or more and 10 μm or less, and an aspect ratio of 4 or more, may be less than 50 parts by mass, less than 30 parts by mass, less than 20 parts by mass, less than 10 parts by mass, or 0 parts by mass. By limiting the content of copper particles with a particle size (maximum diameter) of 0.8 μm or more and 10 μm or less, and an aspect ratio of less than 2, while suppressing the formation of pores in the through holes by the first copper particles in the copper paste, a copper sintered body with a porous structure and a sufficiently formed conductive network can be formed in the through holes or non-through holes. Furthermore, on the main surface of the silicon substrate, the first copper particles are easily oriented approximately parallel to the coating surface of the copper paste, thereby forming a copper sintered body that is less prone to cracking by more effectively suppressing volume shrinkage. When wiring is formed from a conductor containing the copper sintered body, wire breakage caused by thermal stress of the wiring can be further suppressed.
[0263] Based on the total mass of metal particles contained in the copper paste, the content of the first copper particle in the copper paste can be 15% or more by mass, 20% or more by mass, or 50% or more by mass, or it can be less than 85% by mass, less than 70% by mass, or less than 50% by mass. If the content of the first copper particle is within the above range, it is easier to obtain the above effect.
[0264] From the perspective of dispersion stability and oxidation resistance, the first copper particles can be treated with a surface treatment agent. The surface treatment agent can be removed during wire formation (during copper particle sintering). Examples of such surface treatment agents include aliphatic carboxylic acids such as palmitic acid, stearic acid, arachidic acid, and oleic acid; aromatic carboxylic acids such as terephthalic acid, pyromellitic acid, and o-phenoxybenzoic acid; aliphatic alcohols such as cetyl alcohol, stearyl alcohol, cyclohexylisoborneol, and tetraethylene glycol; aromatic alcohols such as p-phenylphenol; alkylamines such as octylamine, dodecylamine, and stearylamine; aliphatic nitriles such as stearonitrile and decanonitrile; silane coupling agents such as alkylalkoxysilanes; and polymeric treatment agents such as polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, and silicone oligomers. A single surface treatment agent can be used, or two or more can be used in combination.
[0265] The amount of surface treatment agent applied to the particle surface can be more than one molecular layer. This amount varies depending on the specific surface area of the first copper particle, the molecular weight of the surface treatment agent, and the minimum coverage area of the surface treatment agent. The amount of surface treatment agent applied is typically 0.001% by mass or more.
[0266] The treatment amount of the surface treatment agent can be determined by the number of molecular layers (n) attached to the surface of the first copper particle and the specific surface area (A) of the first copper particle.p (Unit: m) 2 / g), molecular weight of surface treatment agent (M) s (unit: g / mol), minimum coverage area of surface treatment agent (S) S (Unit: m) 2 / each), Avogadro number (N) A (6.02×10) 23 The amount of surface treatment agent is calculated as follows: (n·A) p ·M s ) / (S S ·N A +n·A p ·M s The formula is calculated as )}×100%.
[0267] The specific surface area of the first copper particle can be calculated by measuring the dried copper particles using the BET specific surface area method. When the surface treatment agent is a straight-chain saturated fatty acid, the minimum coverage area of the surface treatment agent is 2.05 × 10⁻⁶. -19 m 2 / 1 molecule. In the case of other surface treatment agents, the amount can be determined by, for example, calculations based on molecular models or by methods described in "Chemistry and Education" (Kiyoshi Ueda, Jun'o Inafuku, Gen Mori, 40(2), 1992, pp. 114-117). An example of a quantitative method for surface treatment agents is shown. Surface treatment agents can be identified by thermally removed gas / gas chromatography-mass spectrometry analysis of dried powder from copper paste after the dispersion medium has been removed, thereby determining the number of carbon atoms and the molecular weight of the surface treatment agent. The carbon content ratio of the surface treatment agent can be analyzed by carbon content analysis. As a carbon content analysis method, for example, high-frequency induction furnace combustion / infrared absorption method can be cited. The surface treatment dosage can be calculated by the above formula based on the number of carbon atoms, molecular weight and carbon content ratio of the identified surface treatment agent.
[0268] Commercially available copper particles can be used as the first copper particle. Examples of commercially available first copper particles include MA-C025 (manufactured by MITSUI MINING & SMELTING CO.,LTD., average particle size 4.1 μm), 3L3 (manufactured by FUKUDA METALFOIL & POWDER CO.,LTD., average particle size 7.3 μm), 1110F (manufactured by MITSUI MINING & SMELTING CO.,LTD., average particle size 5.8 μm), and 2L3 (manufactured by FUKUDA METAL FOIL & POWDER CO.,LTD., average particle size 9 μm).
[0269] When manufacturing copper paste, copper particles containing a first copper particle with a particle size (maximum diameter) of 0.8 μm or more and 10 μm or less and an aspect ratio of 4 or more, and copper particles with a particle size (maximum diameter) of 0.8 μm or more and 10 μm or less and an aspect ratio of less than 2, can be used. Commercially available products composed of such copper particles can be selected for use.
[0270] From the viewpoint of suppressing volume shrinkage to form a copper sintered body that is less prone to cracking, the ratio of the pore diameter of the through-hole to the particle size (maximum diameter) of the first copper particle (pore diameter (μm) / particle size (maximum diameter) (μm)) can be 4 or more, 8 or more, or 10 or more, or 150 or less, 100 or less, or 50 or less. Regarding non-through-holes, the ratio of the pore diameter of the non-through-hole to the particle size (maximum diameter) of the first copper particle (pore diameter (μm) / particle size (maximum diameter) (μm)) can be set so that the ratio of the pore diameter of the formed silicon through-hole electrode to the particle size (maximum diameter) of the first copper particle (pore diameter (μm) / particle size (maximum diameter) (μm)) is within the above-mentioned range.
[0271] In one embodiment, the copper paste may contain the aforementioned first copper particles and second copper particles with a particle size (maximum diameter) of 0.5 μm or less. In this case, when the copper particles are sintered, the second copper particles are positioned between the first copper particles, thereby improving the conductivity of the resulting wiring. That is, it is preferable to use both the first and second copper particles. When the copper paste is prepared using only the second copper particles, the large volume shrinkage during drying of the dispersion medium and the large sintering shrinkage make it easy for the sintered body to peel off from the metal coating on the silicon wafer when the copper particles are sintered, making it difficult to obtain sufficient airtightness or connection reliability. However, by using both the first and second copper particles, the volume shrinkage during the sintering of the copper paste is suppressed, and the adhesion between the copper sintered body formed in the through-hole and the metal coating formed on the wall surface of the through-hole or non-through-hole can be improved. As a result, it is difficult for cracks caused by thermal stress in the copper sintered body in the through-hole to occur, and the airtightness and connection reliability against thermal stress are further improved.
[0272] The second copper particle can function as a copper particle that appropriately bonds the first copper particles together. Furthermore, the second copper particle has superior sinterability compared to the first copper particle, and can promote the sintering of copper particles. For example, compared to using the first copper particle alone, copper particles can be sintered at a lower temperature. Moreover, when copper paste is prepared using only the second copper particle, the large volume shrinkage associated with drying the dispersion medium and the large sintering shrinkage cause volume shrinkage in the copper sintered body formed inside the through-holes or non-through-holes, thereby easily generating porosity inside the through-holes or non-through-holes. In particular, by using both the flat first copper particle and the second copper particle together, the flat first copper particle functions as a copper particle appropriately bonded by the second copper particle, thereby suppressing the generation of porosity inside the through-holes and easily forming a copper sintered body with a porous structure.
[0273] The average particle size (average maximum diameter) of the second copper particles contained in the copper paste can be greater than 0.01μm, greater than 0.03μm, greater than 0.05μm, greater than 0.08μm, greater than 0.1μm, or greater than 0.2μm, or less than 0.5μm, less than 0.4μm, less than 0.3μm, or less than 0.2μm.
[0274] If the average particle size (average maximum diameter) of the second copper particles is greater than 0.01 μm, it is easy to obtain the effects of reducing the synthesis cost of the second copper particles, good dispersibility, and reducing the amount of surface treatment agent used. If the average particle size (average maximum diameter) of the second copper particles is less than 0.5 μm, it is easy to obtain the effect of excellent sinterability of the second copper particles.
[0275] The second copper particles can contain 20% or more by mass of copper particles with a particle size (maximum diameter) of 0.01 μm or more and 0.5 μm or less. From the viewpoint of the sinterability of the copper paste, the second copper particles can contain 30% or more by mass of copper particles with a particle size of 0.01 μm or more and 0.5 μm or less, or 50% or more by mass, or 85% or less by mass. If the proportion of copper particles with a particle size (maximum diameter) of 0.01 μm or more and 0.5 μm or less in the second copper particles is 20% or more by mass, the dispersibility of the copper particles is further improved, which can further suppress the increase in viscosity and the decrease in paste concentration.
[0276] Based on the total mass of metal particles contained in the copper paste, the content of the second copper particles in the copper paste can be 20% or more by mass, 30% or more by mass, 35% or more by mass, or 40% or more by mass, or it can be less than 85% by mass, less than 80% by mass, or less than 75% by mass. If the content of the second copper particles is within the above range, while suppressing the generation of pores in through holes or non-through holes, a copper sintered body with excellent adhesion to the metal coating disposed on the silicon substrate can be easily formed. A copper sintered body that is not prone to cracking on the main surface of the silicon substrate can be formed. When a conductor containing the copper sintered body is used to form wiring, wire breakage caused by thermal stress of the wiring can be further suppressed.
[0277] Based on the sum of the masses of the first and second copper particles, the content of the second copper particle in the copper paste can be 20% by mass or more, or 85% by mass or less. If the content of the second copper particle is 20% by mass or more, it can fully fill the spaces between the first copper particles and form a copper sintered body that is less prone to cracking. Wiring formed from a conductor containing this copper sintered body is less likely to experience wire breakage due to thermal stress. If the content of the second copper particle is 85% by mass or less, it can sufficiently suppress the volume shrinkage during copper particle sintering, thus suppressing the formation of porosity in through holes or non-through holes, and forming a copper sintered body that is less prone to cracking. Wiring formed from a conductor containing this copper sintered body is less likely to experience wire breakage due to thermal stress.
[0278] From the perspective of more easily achieving the above-mentioned effects, based on the sum of the mass of the first copper particle and the mass of the second copper particle, the content of the second copper particle can be 30% or more by mass, 35% or more by mass, or 40% or more by mass, or it can be less than 85% by mass or less than 80% by mass.
[0279] The shape of the second copper particle can be, for example, spherical, blocky, needle-like, flat (flake-like), or roughly spherical. The second copper particle can be an aggregate of copper particles having these shapes. From the viewpoint of dispersibility and filling properties, the shape of the second copper particle can be spherical, roughly spherical, or flat (flake-like). From the viewpoint of combustibility and mixing with the first copper particle, it can be spherical or roughly spherical.
[0280] From the viewpoint of dispersibility, filling properties, and mixing with the first copper particle, the aspect ratio of the second copper particle can be 5 or less, 4 or less, or 3 or less.
[0281] The second copper particle can be treated with a specific surface treatment agent. Examples of such surface treatment agents include organic acids with 8 to 16 carbon atoms. Examples of organic acids with 8 to 16 carbon atoms include octanoic acid, methylheptanoic acid, ethylhexanoic acid, propylvalerate, nonanoic acid, methyloctanoic acid, ethylheptanoic acid, propylhexanoic acid, decanoic acid, methylnonanoic acid, ethyloctanoic acid, propylheptanoic acid, butylhexanoic acid, undecanoic acid, methyldecanoic acid, ethylnonanoic acid, propyloctanoic acid, butylheptanoic acid, lauric acid, methylundecanoic acid, ethyldecanoic acid, propylnonanoic acid, butyloctanoic acid, pentylheptanoic acid, tridecanoic acid, methyldodecanoic acid, ethylundecanoic acid, propyldecanoic acid, butylnonanoic acid, pentyloctanoic acid, myristic acid, methyltridecanoic acid, ethyldodecanoic acid, propylundecanoic acid, butyldecanoic acid, pentylnonanoic acid, hexyloctanoic acid, pentadecanoic acid, methyltetradecanoic acid, and ethyltridecanoic acid. Saturated fatty acids including propyl dodecanoic acid, butyl undecanoic acid, pentyl decanoic acid, hexyl nonanoic acid, palmitic acid, methyl pentadecanoic acid, ethyl tetradecanoic acid, propyl tridecanoic acid, butyl dodecanoic acid, pentyl undecanoic acid, hexyl decanoic acid, heptyl nonanoic acid, methyl cyclohexane carboxylic acid, ethyl cyclohexane carboxylic acid, propyl cyclohexane carboxylic acid, butyl cyclohexane carboxylic acid, pentyl cyclohexane carboxylic acid, hexyl cyclohexane carboxylic acid, octyl cyclohexane carboxylic acid, and nonyl cyclohexane carboxylic acid; octenic acid, nonenoic acid, methyl nonenoic acid, decenoic acid, undecenoic acid, dodecenoic acid, tridecenoic acid, tetradecenoic acid, myristoleic acid, pentadecenoic acid, hexadecenoic acid, palmitoleic acid, and sapienic acid. Unsaturated fatty acids such as terephthalic acid, pyromellitic acid, o-phenoxybenzoic acid, methyl benzoic acid, ethyl benzoic acid, propyl benzoic acid, butyl benzoic acid, pentyl benzoic acid, hexyl benzoic acid, heptyl benzoic acid, octyl benzoic acid, and nonyl benzoic acid are also present. Organic acids can be used alone or in combination of two or more. By combining this organic acid with the aforementioned second copper particle, it is possible to simultaneously achieve the dispersibility of the second copper particle and the detachment of the organic acid during sintering.
[0282] The amount of surface treatment agent applied can be one to three molecular layers adhering to the surface of the second copper particle. The amount of surface treatment agent can be 0.07% by mass or more, 0.10% by mass or more, or 0.2% by mass or more, or less than 2.1% by mass, less than 1.6% by mass, or less than 1.1% by mass. The surface treatment amount for the second copper particle can be calculated for the first copper particle using the method described above. The specific surface area, molecular weight of the surface treatment agent, and minimum coverage area of the surface treatment agent are also the same.
[0283] As the second copper particle, it is possible to use either synthetic or commercially available particles.
[0284] Based on the total mass of metal particles contained in the copper paste, the sum of the content of the first copper particle and the second copper particle in the copper paste can be 90% by mass or more. If the sum of the content of the first copper particle and the second copper particle is within the above range, it is easy to suppress the formation of porosity in through holes or non-through holes. From the viewpoint of more easily obtaining this effect, based on the total mass of metal particles, the sum of the content of the first copper particle and the second copper particle can be 95% by mass or more, or even 100% by mass.
[0285] Copper paste may also contain other metal particles besides copper particles. Examples of other metal particles include nickel, silver, gold, palladium, and platinum. The average particle size (maximum diameter) of these other metal particles may be 0.01 μm or more, 0.05 μm or more, or less than 5 μm, 3.0 μm or less, or less than 2.0 μm. When other metal particles are included, from the viewpoint of obtaining sufficient bonding strength, their content, based on the total mass of the metal particles contained in the copper paste, may be less than 20% by mass or less than 10% by mass. It is also possible to omit other metal particles. The shape of the other metal particles is not particularly limited.
[0286] The dispersion medium contained in copper paste is not particularly limited; for example, it can be a volatile dispersion medium. Examples of volatile dispersion media include mono- and polyols such as pentanol, hexanol, heptanol, octanol, decanol, ethylene glycol, diethylene glycol, propylene glycol, butanediol, α-terpineol, and cyclohexaneisoborneol (MTPH); ethylene glycol butyl ether, ethylene glycol phenyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, diethylene glycol isobutyl ether, diethylene glycol hexyl ether, triethylene glycol methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, diethylene glycol isopropyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol butyl methyl ether, propylene glycol propyl ether, dipropylene glycol methyl ether, dipropylene glycol ethyl ether, dipropylene glycol propyl ether, and dipropylene glycol. Ethers such as butyl ether, dipropylene glycol dimethyl ether, tripropylene glycol methyl ether, and tripropylene glycol dimethyl ether; esters such as ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, dipropylene glycol methyl ether acetate (DPMA), ethyl lactate, butyl lactate, γ-butyrolactone, and propylene carbonate; acid amides such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide; aliphatic hydrocarbons such as cyclohexane, octane, nonane, decane, and undecane; aromatic hydrocarbons such as benzene, toluene, and xylene; thiols with alkyl groups having 1 to 18 carbon atoms; and thiols with cycloalkyl groups having 5 to 7 carbon atoms. Examples of thiols having alkyl groups with 1 to 18 carbon atoms include ethyl thiols, n-propyl thiols, isopropyl thiols, n-butyl thiols, isobutyl thiols, tert-butyl thiols, pentyl thiols, hexyl thiols, and dodecyl thiols. Examples of thiols having cycloalkyl groups with 5 to 7 carbon atoms include cyclopentyl thiols, cyclohexyl thiols, and cycloheptyl thiols.
[0287] The total mass of metal particles contained in the copper paste is set to 100 parts by mass. The content of the dispersion medium can be more than 3 parts by mass, more than 4 parts by mass, or more than 5 parts by mass, or less than 20 parts by mass, less than 16 parts by mass, or less than 12 parts by mass. If the content of the dispersion medium is within the above range, the copper paste can be adjusted to a more suitable viscosity, and the formation of pores in the through holes can be easily suppressed.
[0288] Depending on the needs, wetting modifiers such as nonionic surfactants and fluorinated surfactants, defoamers such as silicone oils, and ion trapping agents such as inorganic ion exchangers can be appropriately added to copper paste.
[0289] The aforementioned copper paste can be prepared by mixing copper particles and any other components (additives, other metal particles, etc.) with a dispersion medium. After mixing the components, stirring can be performed. The maximum diameter of the dispersion can be adjusted through a fractionation process.
[0290] A dispersion of the second copper particles is prepared by pre-mixing a second copper particle, a surface treatment agent, and a dispersion medium, followed by dispersion treatment. The first copper particle, other metal particles, and any additives are then further mixed to prepare copper paste. By following this sequence, the dispersibility of the second copper particle is improved to optimize its miscibility with the first copper particle, further enhancing the performance of the copper paste. Aggregates can also be removed by providing the dispersion of the second copper particle to a fractionation process.
[0291] Example
[0292] The present invention will now be described in more detail through embodiments. However, the present invention is not limited to the following embodiments.
[0293] (Synthesis of the second copper particle)
[0294] Synthesis of copper nonanoate
[0295] 91.5 g (0.94 mol) of copper hydroxide (KANTO CHEMICAL CO., INC., premium grade) was mixed with 150 mL of 1-propanol (KANTO CHEMICAL CO., INC., premium grade), and then 370.9 g (2.34 mol) of nonanoic acid (KANTO CHEMICAL CO., INC., ≥90%) was added. The resulting mixture was heated in a separating flask at 90 °C and stirred for 30 minutes. The resulting solution was filtered while heated to remove undissolved matter. Then, after natural cooling, the resulting copper nonanoate was filtered and washed with hexane until the washing solution became clear. The resulting powder was dried in an explosion-proof oven at 50 °C for 3 hours to obtain copper nonanoate(II). The yield was 340 g (96% by mass).
[0296] [Synthesis of the second copper particle]
[0297] 15.01 g (0.040 mol) of copper(II) nonanoate and 7.21 g (0.040 mol) of copper(II) acetate anhydride (KANTO CHEMICAL CO., INC., premium grade) were added to a separating flask, along with 22 mL of 1-propanol and 32.1 g (0.32 mol) of hexylamine (Tokyo Chemical Industry Co., Ltd., 99% purity). The mixture was heated and stirred in an oil bath at 80 °C to dissolve the copper(II) nonanoate. The mixture was then transferred to an ice bath and cooled to an internal temperature of 5 °C. 7.72 mL (0.16 mol) of hydrazine monohydrate (KANTO CHEMICAL CO., INC., premium grade) was added and stirred in the ice bath. The molar ratio of copper to hexylamine was 1:4. The mixture was then heated and stirred in an oil bath at 90 °C. A reduction reaction accompanied by foaming occurred, and the reaction was completed within 30 minutes. The inner wall of the separation flask has a coppery luster, and the solution turns dark red. Centrifugation at 9000 rpm for 1 minute yields a solid. The solid is then washed three times with 15 mL of hexane to remove acid residue, resulting in copper-colored powder particles (second copper particles).
[0298] The synthesized copper particles were observed using a transmission electron microscope (manufactured by JEOL Co., Ltd., product name: JEM-2100F). The average long axis of 200 randomly selected copper particles was 104 nm. The second particle was spherical.
[0299] (Preparation of copper paste)
[0300] <Examples 1-73>
[0301] Copper paste was prepared by mixing the raw materials shown below in the proportions shown in Tables 1 to 8.
[0302] [First Copper Particle]
[0303] Flat 1.4μm: 1100YP (manufactured by MITSUI MINING & SMELTING CO.,LTD., average particle size 1.4μm (D50), product name)
[0304] Flat 3.1μm: 1200YP (manufactured by MITSUI MINING & SMELTING CO.,LTD., average particle size 3.1μm (D50), product name)
[0305] Flat 5.8μm: MA-C05KP (manufactured by MITSUI MINING & SMELTING CO.,LTD., average particle size 5.8μm (D50), product name)
[0306] Flat 7.3μm: MA-C05KFD (manufactured by MITSUI MINING & SMELTING CO.,LTD., average particle size 7.3μm (D50), product name)
[0307] [Second copper particle]
[0308] Spherical 100nm: The copper particles synthesized above
[0309] Spherical 250nm: CH0200 (manufactured by MITSUI MINING & SMELTING CO.,LTD., D50 250nm, product name)
[0310] (other)
[0311] Diethylene glycol (manufactured by FUJIFILM Wako Pure Chemical Corporation)
[0312] <Comparative Example 1>
[0313] Copper paste was prepared by mixing 70 parts by mass of 1100YP (manufactured by MITSUI MINING & SMELTING CO.,LTD., average particle size 1.4 μm (D50), product name) as the first copper particle, 30 parts by mass of the above-synthesized copper particles as the second copper particle, 5 parts by mass of diethylene glycol (manufactured by FUJIFILM Wako Pure Chemical Corp.), and 5 parts by mass of resin components. As the resin component, a resin component was used that was a mixture of acrylic resin (an organic binder) and carbitol and terpineol (organic solvents) at a mass ratio of 1:2.
[0314] (Preparation process for silicon substrate)
[0315] <Examples 1-73 and Comparative Example 1>
[0316] A silicon substrate with through-holes was prepared, and titanium, nickel, and copper layers were sequentially formed on the two main surfaces and the walls of the through-holes. The silicon substrate had a diameter of 6 inches and a thickness of 500 μm. The apertures of the through-holes in the silicon substrate are shown in Tables 1-8. The titanium, nickel, and copper layers were formed sequentially by sputtering.
[0317] (Copper sintering body formation process)
[0318] <Examples 1-8, 12-21, 24-43, 48-73 and Comparative Example 1>
[0319] The prepared copper paste was applied to both main surfaces of the silicon substrate using a metal scraper, and the copper paste was also used to fill the through-holes. After application, the copper paste was dried in the atmosphere at 90°C for 10 minutes. After drying, a copper paste layer with a thickness of 30 μm was formed on the silicon substrate.
[0320] A silicon substrate with a copper paste layer was pressurized from both sides using a pressure fixture. The pressure applied to the silicon substrate during pressurization was specified in Tables 1-8. The pressure fixture, equipped with a flat aluminum plate and springs, allowed for adjustment of the pressure. The silicon substrate, pressurized by the fixture, was placed in a tube furnace (manufactured by AVC Co.,LTD.), and argon gas was passed through it at a rate of 1 L / min to replace the air in the tube furnace. Then, hydrogen gas was passed through it at a rate of 300 mL / min while the temperature was increased for 10 minutes, and sintering was performed at 300°C for 60 minutes, thereby sintering the copper paste. The argon gas flow rate was then reduced to 0.3 L / min for cooling, and the substrate was removed and exposed to air at a temperature below 50°C, resulting in a copper-filled sintered body on the silicon substrate. The thickness of the copper sintered body formed on the two main surfaces of the sintered silicon substrate was 25 μm.
[0321] <Examples 9-11>
[0322] The silicon substrate was not pressurized by a pressure fixture, but a copper sintered body was obtained filling the silicon substrate in the same manner as in Example 1. The thickness of the copper sintered body formed on the two main surfaces of the silicon substrate after sintering was 35 μm.
[0323] <Examples 22 and 23>
[0324] During the sintering process, nitrogen gas was used instead of hydrogen gas to flow through the silicon substrate, and otherwise, a copper sintered body was obtained to fill the silicon substrate in the same manner as in Example 1. The thickness of the copper sintered body formed on the two main surfaces of the sintered silicon substrate was 30 μm.
[0325] <Examples 44-47>
[0326] Sintering was performed at heating times of 10 minutes, 225°C, and 60 minutes. Otherwise, a copper sintered body filled with a silicon substrate was obtained in the same manner as in Example 1. The thickness of the copper sintered body formed on the two main surfaces of the sintered silicon substrate was 30 μm.
[0327] (Determination of porosity in copper sintered bodies)
[0328] <Examples 1-73 and Comparative Example 1>
[0329] Using a focused ion beam processing observation apparatus (manufactured by Hitachi High-Technologies Corporation, product name: MI4050), the cross-sections of the central portion of a through-hole in a silicon substrate and the cross-section of a copper sintered body disposed on the main surface of the silicon substrate were exposed by a focused ion beam, and these cross-sections were observed. When observing the cross-section of the central portion of the through-hole, a range of ±5 μm in the thickness direction of the silicon substrate and a range of ±5 μm in the direction orthogonal to the thickness direction of the silicon substrate were observed from the center of the copper sintered body filling the through-hole. When observing the cross-section of the copper sintered body disposed on the main surface of the silicon substrate, a range of 10 μm in the thickness direction of the silicon substrate and a range of 10 μm in the direction orthogonal to the thickness direction of the silicon substrate were observed from the surface of the copper sintered body formed on the main surface of the silicon substrate to a depth of 5 μm.
[0330] A scanning electron microscope (Hitachi High-Technologies Corporation, product name: S-3700N) was used for observation at a magnification of 10,000x, and cross-sectional images (approximately 10 μm angle) of the copper sintered body were captured. Five observation sites were selected. The obtained cross-sectional images were binarized using image analysis software (Adobe Photoshop Elements) to separate the sintered copper portion from the porous portion. The binarized cross-sectional images are shown below. Figure 9 In the observation of each of the five locations, the porosity was defined as the ratio of the area of the porous portion to the total cross-sectional area of the copper sintered body. The average porosity observed at the five locations was defined as the porosity of the copper sintered body. The results are shown in Tables 1-8.
[0331] (Resin impregnation process)
[0332] <Examples 1-73>
[0333] The curable resin composition described below is applied to one side of a copper sintered silicon substrate using a roller coater. Next, the copper sintered silicon substrate is placed in a container, and the container is evacuated to a gauge pressure of 100 kPa, creating a vacuum. The copper sintered silicon substrate is held under vacuum for 10 minutes, and then removed from the container. It is confirmed that the curable resin composition is impregnated in the copper sintered body through the through-holes, reaching the side of the copper sintered body opposite to the side coated with the curable resin composition. Any remaining curable resin composition on the coated surface of the copper sintered silicon substrate is removed using a rubber scraper. Then, on the side opposite to the side coated with the curable resin composition, the curable resin composition is applied using a roller coater, and any remaining curable resin composition on the surface of the copper sintered silicon substrate is vigorously removed using a rubber scraper.
[0334] [Curing Resin Composition]
[0335] YDF-170 (manufactured by TOHTO Chemical Industry Co., Ltd., product name of bisphenol F type epoxy resin, epoxy equivalent = 170): 95 parts by weight
[0336] 2PZ-CN (SHIKOKU CHEMICALS CORPORATION, manufacturer of imidazole compounds): 5 parts by weight
[0337] <Comparative Example 1>
[0338] The resin impregnation process was not performed.
[0339] (Resin curing process)
[0340] <Examples 1-73>
[0341] A silicon substrate with a silicon through electrode is obtained by impregnating a curable resin composition in a copper sintered body and holding it at 180°C for 1 hour in a nitrogen environment.
[0342] <Comparative Example 1>
[0343] The resin curing process was not performed.
[0344] (Conductor removal process)
[0345] <Examples 1-73 and Comparative Example 1>
[0346] Both sides of the substrate with silicon through-electrodes were mechanically polished until the thickness of the copper sintered body on both sides of the substrate with silicon through-electrodes reached 20 μm. A ceramic fixture (manufactured by Kemet Japan Co., Ltd.) was used as the sample stage for attaching the substrate with silicon through-electrodes, and ALCOWAX (manufactured by NIKKA SEI KO CO.,LTD.) was used as the abrasive. Furthermore, DP-suspension P-3μm·1μm·1 / 4μm (manufactured by Struers Co., Ltd.) was used sequentially.
[0347] [Filling rate of cured resin in conductor]
[0348] <Examples 1-73 and Comparative Example 1>
[0349] A substrate with silicon through-hole electrodes, which had undergone mechanical polishing, was cut along its thickness. A focused ion beam was used to expose the cross-sections of the central portion of the through-hole and the cross-sections of the conductors disposed on the main surface of the silicon substrate, and these cross-sections were observed. When observing the cross-section of the central portion of the through-hole, a range of ±5 μm along the thickness direction of the silicon substrate and a range of ±5 μm in a direction orthogonal to the thickness direction of the silicon substrate were observed. When observing the cross-section of the conductors disposed on the main surface of the silicon substrate, a range of 10 μm along the thickness direction of the silicon substrate and a range of 10 μm in a direction orthogonal to the thickness direction of the silicon substrate were observed in the region from the surface of the conductors on the main surface of the silicon substrate to 5 μm. The focused ion beam processing observation apparatus used was a Hitachi High-Technologies Corporation (product name: MI4050). A scanning electron microscope (Hitachi High-Technologies Corporation (product name: S-3700N)) was used for observation, with a magnification of 10,000x, and cross-sectional images of the conductors (approximately 10 μm angle) were captured. Five observation sites were set. The obtained cross-sectional images were binarized using image analysis software (Adobe Photoshop Images) to separate the unfilled spaces in the sintered copper portion, the resin-cured portion, and the porous portion. For each of the five observation sites, the ratio of the area of the unfilled space in the porous portion to the total area of the conductor cross-section was calculated and set as the porosity. The average porosity of the five observed sites was set as the porosity of the conductor. The porosity of the sintered copper body and the porosity of the conductor were substituted into the following equation (1) to calculate the resin-cured filling rate in the conductor.
[0350] The filling rate (%) of the cured resin in the conductor = [(BA) / B] × 100……Equation (1)
[0351] [In formula (1), A represents the porosity (%) of the conductor, and B represents the porosity (%) of the copper sintered body.]
[0352] (Wire forming process (resist formation, etching, and resist removal))
[0353] <Examples 1-73 and Comparative Example 1>
[0354] On the surfaces of a copper sintered body with silicon through electrodes on both sides of a substrate that has undergone mechanical polishing, a UV-curable etch resist dry film H-W425 (manufactured by Hitachi Chemical Co., Ltd., product name) was laminated. Then, a wiring pattern was exposed using a photomask, and the wiring was formed through a process of resist development, etching of the copper sintered body, and resist removal. Figure 10 The substrate (test piece 55) shown has silicon through-hole electrodes. In the obtained substrate (test piece 55) with silicon through-hole electrodes, the conductors filling the through-holes are electrically connected by conductors (wiring) disposed on the surface of the substrate.
[0355] (Initial resistance value)
[0356] <Examples 1-73 and Comparative Example 1>
[0357] As the initial resistance value of the substrate (test piece 55) with silicon through-hole electrodes, the connection resistance value was measured. The resistance values of 20 through-hole connections were measured when the diameter of the through-hole in the silicon substrate was 20 μm; the resistance values of 30 through-hole connections were measured when the diameter of the through-hole in the silicon substrate was 30 μm; the resistance values of 30 through-hole connections were measured when the diameter of the through-hole in the silicon substrate was 50 μm; the resistance values of 100 through-hole connections were measured when the diameter of the through-hole in the silicon substrate was 100 μm; and the resistance values of 200 through-hole connections were measured when the diameter of the through-hole in the silicon substrate was 200 μm. The measured connection resistance values were evaluated according to the following criteria. An evaluation of B or higher was judged as good. The results are shown in Tables 1 to 8.
[0358] A: Resistance value is less than 10mΩ
[0359] B: Resistance value is above 10mΩ and below 30mΩ
[0360] C: Resistance value is 30mΩ or higher and less than 100mΩ
[0361] D: Resistance value is above 100mΩ and less than 500mΩ
[0362] E: Resistance value above 500mΩ
[0363] (Temperature Cycling Connectivity Test)
[0364] <Examples 1-73 and Comparative Example 1>
[0365] A substrate with a silicon through-electrode (test piece 55) was placed in a temperature cycling test chamber (TSA-72S EW, manufactured by ESPEC CORP.) and a temperature cycling connection reliability test was performed under the following conditions: low temperature side: -40°C, 15 minutes; room temperature side: 2 minutes; high temperature side: 125°C, 15 minutes; defrost cycle: automatic; number of cycles: 50, 100, 300, 500. The resistance values of 20 interconnected vias were measured when the via diameter was 20 μm in the silicon substrate; the resistance values of 30 interconnected vias when the via diameter was 30 μm in the silicon substrate; the resistance values of 30 interconnected vias when the via diameter was 50 μm in the silicon substrate; the resistance values of 100 interconnected vias when the via diameter was 100 μm in the silicon substrate; and the resistance values of 200 interconnected vias when the via diameter was 200 μm in the silicon substrate. The measured interconnection resistance values were evaluated according to the following criteria. If the evaluation after 500 temperature cycling tests is B or higher, it is judged as good. The results are shown in Tables 1 to 8.
[0366] A: The rate of change in resistance relative to the initial resistance value is less than 1%.
[0367] B: The rate of change of resistance relative to the initial resistance value is greater than 1% and less than 3%.
[0368] C: The rate of change of resistance relative to the initial resistance value is greater than 3% and less than 5%.
[0369] D: The rate of change of resistance relative to the initial resistance value is greater than 5% and less than 10%.
[0370] E: The rate of change of resistance relative to the initial resistance value is greater than 10% and less than 20%.
[0371] F: The rate of change of resistance relative to the initial resistance value is 20% or more.
[0372] (Cracks in the substrate)
[0373] <Examples 1-73 and Comparative Example 1>
[0374] Visually inspect the substrate with the silicon through-electrode (test piece 55) to confirm the presence or absence of silicon substrate cracks. Cases without cracks are rated ○, and cases with localized cracks are rated ×. The results are shown in Tables 1-8.
[0375] (Air tightness)
[0376] <Examples 1-73 and Comparative Example 1>
[0377] The hermeticity of the substrate with silicon through-electrodes (test piece 55) was evaluated. The evaluation was performed using a helium leak detector (LEYBOLD "UL200"). Specifically, the substrate with silicon through-electrodes was placed on a fixture, and a vacuum was applied until the inlet pressure of the testing machine reached 5 Pa. After a 30-second pressurization with He (0.1 MPa) at the moment the inlet pressure reached 5 Pa, the leakage was measured, and the results were evaluated according to the following criteria. The results are shown in Tables 1-8.
[0378] A: Leakage amount is less than 1×10 -11 Pa·m 3 / sec
[0379] B: The leakage amount is 1×10 -11 Above and less than 1×10 -10 Pa·m 3 / sec
[0380] C: Leakage amount is 1×10 -10 Above and less than 1×10 -9 Pa·m 3 / sec
[0381] D: Leakage amount is 1×10 -9 Above and less than 1×10 -8 Pa·m 3 / sec
[0382] E: Leakage amount is 1×10 -8 Above and less than 1×10 -6 Pa·m 3 / sec
[0383] F: Leakage amount is 1×10 -6 Pa·m 3 / sec or more.
[0384] (Wiring tightness - tensile strength -)
[0385] <Examples 1-73 and Comparative Example 1>
[0386] For a substrate with a silicon through electrode obtained in the same manner except for forming a 2mm×2mm wiring pattern in the wiring formation process, the front end area is 1mm². 2 The stud pins were vertically joined by welding and used as test pieces. The test pieces were fixed, and the stud pins were gripped by the chuck of a tensile testing machine. The machine was stretched vertically upwards at an upward speed of 50 mm / min, and the failure load when the copper sintered layer on the main surface of the silicon substrate was measured. Then, based on the measured failure load and the failure area of the copper sintered layer, the adhesion strength was calculated using the following formula. Furthermore, the measured values were set as the average of 10 points and evaluated according to the following criteria. The results are shown in Tables 1-8.
[0387] Adhesion strength (MPa) = Breaking load (kgf) / Breaking area (mm²) 2 )×9.8(N / kgf).
[0388] A: The bonding strength (MPa) is above 50MPa.
[0389] B: Adhesion strength (MPa) is above 40MPa and less than 50MPa
[0390] C: Adhesion strength (MPa) is 30 MPa or higher and less than 40 MPa
[0391] D: Adhesion strength (MPa) is above 20MPa and less than 30MPa
[0392] E: Adhesion strength (MPa) is 5 MPa or higher and less than 20 MPa
[0393] F: Adhesion strength (MPa) less than 5MPa
[0394] (Wireforming characteristics - presence or absence of cracks)
[0395] <Examples 1-73 and Comparative Example 1>
[0396] Substrates with silicon through-electrodes, obtained in the same manner except for the formation of five 2mm × 2mm wiring patterns in the wiring formation process, were observed using an optical microscope. The presence or absence of cracks (length greater than 0.5mm) in the wiring patterns was observed. The magnification was set to 500x, and the evaluation was performed according to the following criteria. The results are shown in Tables 1–8.
[0397] A: No cracks were formed.
[0398] B: There is one or more cracks but fewer than two.
[0399] C: There are 2 or more cracks but fewer than 5 cracks
[0400] D: There are 5 or more cracks but less than 10 cracks
[0401] E: There are 10 or more cracks but less than 20 cracks
[0402] F: More than 20 cracks
[0403] (Volume resistivity)
[0404] <Examples 1-73 and Comparative Example 1>
[0405] The volume resistivity of the conductor formed on the silicon substrate was measured. The volume resistivity was calculated from the surface resistance measured using a four-pin surface resistivity meter (manufactured by MITSUBISHI MATERIALS CHEMICALS Corporation, product name: LorestaGP) and the film thickness determined using a non-contact surface / layer cross-sectional shape measurement system (VertScan, Mitsubishi Chemical Systems, Inc.). The results are shown in Tables 1–8.
[0406]
[0407]
[0408]
[0409]
[0410]
[0411]
[0412]
[0413] [Table 8]
[0414]
[0415] Symbol Explanation
[0416] 1-Silicon wafer, 2-Metal coating, 3-Copper paste, 4-Porous, 5-Copper sintered body, 6-Cure resin, 8-Etching resist, 9-Wire, 15-Micro bump, 20-Cure adhesive, 25-Intercalation substrate, 27-Wire, 30-Through hole, 31-Non-Through hole, 35-Conductor, 40, 41-Silicon substrate, 50, 60-Copper sintered body filled silicon substrate, 51, 52, 61-Substrate with silicon through-electrode, 55-Test piece, 100, 200, 300-Semiconductor device, A-Pressure clamp.
Claims
1. A method for manufacturing a substrate having a silicon through-electrode, comprising: The preparation process involves preparing a silicon substrate, which includes a silicon wafer with through holes, the through holes being formed on two main surfaces. The copper sintered body forming process forms a copper sintered body with a porous structure by at least filling the through holes; The resin impregnation process involves impregnating the copper sintered body with a curable resin composition; and The resin curing process involves curing the curable resin composition impregnated in the copper sintered body to form a conductive body comprising a copper sintered body with pores filled with cured resin. Silicon through-hole electrodes are disposed within the through-holes. The manufacturing method uses copper paste containing first copper particles with a particle size of 0.8 μm or more. The ratio of the aperture of the through hole to the particle size of the first copper particle in terms of its maximum diameter, i.e., aperture / particle size in terms of maximum diameter, is 4 or more and 150 or less. The units for aperture and particle size are μm.
2. A method for manufacturing a substrate having a silicon through-electrode, comprising: Preparation process: Prepare a silicon substrate, which includes a silicon wafer having non-through holes, with the non-through holes opening on a main surface; The copper sintered body forming process forms a copper sintered body with a porous structure by at least filling the non-penetrating holes; The resin impregnation process involves impregnating the copper sintered body with a curable resin composition; and The resin curing process involves curing the curable resin composition impregnated in the copper sintered body to form a conductive body comprising a copper sintered body with porous structures filled with cured resin; and In the grinding process, a silicon through-hole electrode is formed by grinding the side of the silicon substrate on which the conductor is formed, opposite to the side with the opening of the non-through-hole. The manufacturing method uses copper paste containing first copper particles with a particle size of 0.8 μm or more. The ratio of the pore size of the non-penetrating hole to the particle size of the first copper particle with the maximum diameter is set such that the ratio of the pore size of the formed silicon through-hole electrode to the particle size of the first copper particle, i.e., the ratio of pore size to particle size with the maximum diameter, is 4 or more and 150 or less. The units for pore size and particle size are μm.
3. The method according to claim 1 or 2, wherein, Based on the volume of the porous internal space, the filling rate of the resin cured material in the conductor is 80% or more by volume.
4. The method according to claim 1 or 2, wherein, Based on the volume of the copper sintered body, the porosity of the copper sintered body is 1 to 15% by volume.
5. The method according to claim 1 or 2, wherein, In the copper sintered body forming process, the copper sintered body is formed in such a way that it covers at least a portion of the main surface of the silicon substrate.
6. The method according to claim 5, further comprising a conductor removal step, the conductor removal step removing at least a portion of the conductor formed on the main surface of the silicon substrate.
7. The method according to claim 6, wherein, The removal method in the conductor removal process is selected from one or more of the group consisting of etching, mechanical polishing and chemical mechanical polishing.
8. The method according to claim 1 or 2, wherein, The silicon substrate has a metal coating at least on the wall surface of the through hole.
9. The method according to claim 1 or 2, wherein, The ratio of the length L of the silicon through-electrode to the aperture D, L / D, is 10 or more.
10. The method according to claim 1 or 2, wherein, The copper sintering body forming process includes: A copper paste filling process, wherein the copper paste containing the first copper particles is filled into the through-holes of the silicon substrate; and The copper paste firing process involves firing the copper paste to form the copper sintered body.
11. The method according to claim 10, wherein, The copper paste further comprises a second copper particle with a particle size of less than 0.5 μm.
12. The method according to claim 11, wherein, The first copper particle is flat.
13. The method according to claim 10, wherein, The copper paste is fired under pressure above 0.1 MPa.
14. The method of claim 10, wherein, The copper paste is fired in an environment containing nitrogen or hydrogen.
15. A substrate having a silicon through-electrode manufactured by the manufacturing method of any one of claims 1 to 14, comprising: A silicon substrate, comprising a silicon wafer having through-holes, the through-holes extending through two main surfaces; and A silicon through-hole electrode, comprising a conductor filling the through-hole. The conductor comprises a copper sintered body with a porous structure and a cured resin filling the pores of the copper sintered body.
16. The substrate having a silicon through-electrode according to claim 15, wherein, Based on the volume of the porous internal space, the filling rate of the resin cured material in the conductor is 80% or more by volume.
17. The substrate having a silicon through-electrode according to claim 15 or 16, wherein, The silicon substrate has a metal coating at least on the wall surface of the through hole.
18. The substrate having a silicon through-electrode according to claim 15 or 16, wherein, The ratio of the length L of the silicon through-electrode to the aperture D, L / D, is 10 or more.
19. The substrate having a silicon through-electrode according to claim 15 or 16, wherein, The conductor covers at least a portion of the main surface of the silicon substrate.
Citation Information
Patent Citations
Method for manufacturing semiconductor device including silicon through electrode and semiconductor device including silicon through electrode
JP2019016712A
Electronic parts and mfg. method therefor
CN1311513A
Manufacturing method of through hole electrode substrate
JP2012119611A